Process for synthesis of graded ordered crystalline microporous materials with long-range mesoporous orderliness

Through the alkali-mediated recombination method and the use of supramolecular templates, the problem of pore disorder in the prior art is solved, and the efficient synthesis of zeolites with long-range mesoporous order is achieved, which improves its catalysis Performance and stability.

CN119486969APending Publication Date: 2025-02-18SAUDI ARABIAN OIL CO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380051852.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-09
Filing Date
2023-06-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult to effectively synthesize zeolites with clearly defined long-range mesoporous order, resulting in randomness in mesoporous size, position and order.

Method used

Through a alkali-mediated recombination method, the parent material is dissolved to the level of oligomeric structure construction units, and the dissolution and self-assembly process is controlled under hydrothermal treatment conditions using supramolecular templates and ionic cosolates to form a highly long-range mesoporous order zeolites of graded order.

Benefits of technology

The efficient synthesis of zeolites with graded order is achieved, which significantly improves the long-range order of its mesoporous structure and enhances the catalytic performance and hydrothermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227802570000401
    Figure BDA0005227802570000401
  • Figure BDA0005227802570000402
    Figure BDA0005227802570000402
  • Figure BDA0005227802570000411
    Figure BDA0005227802570000411
Patent Text Reader

Abstract

Methods for the synthesis of graded ordered zeolites and zeolitic-type materials are provided. The synthetic hierarchically ordered zeolites and zeolite-type materials formed according to the methods herein have a high degree of well-defined long-range mesoporous orderliness. The method includes base-mediated recombination by dissolving the parent material to the level of oligomeric structural building units of the parent material and minimizing or avoiding amorphization / structural collapse. According to the methods herein, solubilization and self-assembly are comprehensively controlled to produce graded ordered zeolites and zeolite-type materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to methods for the synthesis of hierarchically ordered crystalline microporous materials. Background Art

[0002] Zeolite

[0003] Zeolites are microporous aluminosilicate materials with a well-defined structure and can be nano- or The uniform pore size (pores typically up to about ). Typically, zeolites include framework atoms such as silicon, aluminum and oxygen arranged as tetrahedra of silicon dioxide and aluminum oxide. Zeolites are generally hydrated aluminosilicates that can be prepared or selected to have controlled porosity and other features, and typically contain cations, water and / or other molecules located in a porous network. There are hundreds of natural and synthetic zeolite framework types with a wide range of applications. Many zeolites occur naturally and are widely mined, and a large number of interdependent studies have produced a large number of synthetic zeolites with different structures and compositions. The unique properties of zeolites and the ability to customize zeolites for specific applications have led to zeolites being widely used in industry as catalysts (e.g., catalytic cracking of hydrocarbons or as components in catalytic converters), molecular sieves, adsorbents (e.g., desiccants), ion exchange materials (e.g., water softening) and for the separation of gases. Some types of zeolites can be used in various processes and many other applications in refineries. Zeolite pores can form sites for catalytic reactions, and can also form channels for some compounds and / or isomers that are selectively excluded from other compounds and / or isomers. Zeolites may also be provided with acidity levels that enhance their effectiveness as catalytic materials or adsorbents, either alone or with the addition of active components. Described below is only one of the hundreds of types of zeolites identified by the International Zeolite Association (IZA). The properties and uses of many of these are well known.

[0004] Zeolite Y (also known as Na-Y zeolite or Y-type faujasite) is a well-known material that has ion exchange, catalytic and adsorption properties. Zeolite Y is also a useful starting material for the production of other zeolites, such as ultrastable Y-type zeolite (USY). Like typical zeolites, faujasite is synthesized from alumina and silica sources, dissolved in an alkaline aqueous solution and crystallized. Faujasite has a framework designated FAU by the IZA and is formed of a 12-ring structure consisting of about The pore opening diameter of the super cage and has about Faujasite is characterized by a three-dimensional pore structure with pores extending perpendicular to each other in the x, y, and z planes. The secondary building units can be positioned at 4, 6, 6-2, 4-2, 1-4-4, or 6-6. Examples of faujasite have a silica to alumina ratio (SAR) ranging from about 2 to about 6, with typical unit cell sizes (units a, b, and c) ranging from about 24.25 to about 10. When the SAR is about 2-3, the faujasite is typically considered to be type X, and when the SAR is greater than about 3, such as about 3-6, the faujasite is typically considered to be type Y. Typically, the faujasite is in the sodium form and can be ion exchanged with ammonium, and the ammonium form can be calcined to convert the zeolite to its proton form.

[0005] Mesoporous silica

[0006] Although zeolites have great utility in their ability to select between small molecules and different cations, mesoporous solids (between about 20 and The pores between the microporous zeolite and the nanoporous zeolite provide the possibility for the application of species that are up to an order of magnitude larger in size, such as nanoparticles and enzymes. The relatively bulky nature of such species hinders diffusion through the microporous zeolite network, and therefore, larger porous systems are required to effectively perform similar molecular sieving effects on larger species.

[0007] Mesoporous silica is amorphous; however, it is the pores that possess long-range order with a periodically arranged pore structure and uniform pore size on the mesoscale. Mesoporous silica offers high surface area and can be used as a host material to introduce additional functionality for a diverse range of applications such as adsorption, separation, catalysis, drug delivery, and energy conversion and storage.

[0008] Ordered structure

[0009] An attractive property of ordered structures is that their architecture can be described relative to their symmetry. The regular form of a crystal is associated with the regular arrangement of the subunits comprising the crystal, and therefore, the symmetry of the crystal is related to the symmetry of the subunits. For example, seven different three-dimensional crystal units are provided in Table 1. Crystal systems can be subdivided according to the symmetry elements (collectively referred to as point groups) present, and are provided in Table 2. For example, 3m infers that there is a mirror plane with a triple axis. For 3 / m (or 6) classes, the mirror plane is perpendicular to the triple axis. In a 2D space with a dimension less than 3D, such as a layered system, there are four crystal systems: hexagonal, square, rectangular and oblique.

[0010] Hierarchically ordered zeolites

[0011] The well-defined microporous structure of zeolite provides a mixture (amalgam) of important physicochemical functions highly expected in various industrial practices. Their pore channels with molecular sizes embedded with adjustable acid / base sites can geometrically distinguish the entry of guest species and direct shape selectivity conversion. Such remarkable properties uniquely shown by zeolite have proved unprecedented importance in many chemical technologies (including but not limited to oil refining, detergent and effluent elimination), which have profound impacts on global economy and environment. However, zeolite performance is often hindered by the poor mass transfer capacity caused by their configuration diffusion in narrow micropores. Therefore, it is important to alleviate inherent mass transfer limitations for exploring the full potential of zeolite in different energy economies, thereby enhancing the accessibility to internal functional sites. Other disadvantages of microporous zeolites as catalysts in some reactions are their sensitivity to coking, which can cause accelerated deactivation and product selectivity of catalysts.

[0012] In this regard, hierarchically ordered zeolites (HOZ) with an ordered mesoporous structure and zeolitized mesopore (mesopore) walls are of great technological importance due to their excellent properties. The HOZ contains layers of different porosities (i.e., mesopores and micropores). Hierarchically ordered zeolites offer advantages over conventional microporous zeolites by, for example, improving diffusion of guest species to active sites, overcoming steric limitations, improving product selectivity, reducing coke formation, improving hydrothermal stability, and improving accessibility of Bronsted and Lewis acid sites; and concomitantly, improved catalytic performance.

[0013] Many synthetic strategies for producing hierarchical zeolites are known and fall into two major categories: bottom-up approaches, including the use of hard and soft templates, and top-down approaches, which typically involve post-synthetic processing. Bottom-up strategies generally involve template techniques used in situ during zeolite crystallization, such as the use of hard templates (carbon sources) or soft templates (surfactants). Top-down strategies generally involve post-synthetic modification of already formed zeolite crystals, for example, by steaming, dealumination (using acids) or desiliconization (using bases). A disadvantage of known processes for producing hierarchically ordered zeolites is that the long-range order of the mesophase in the resulting zeolite is limited or non-existent, and the mesopores can be random in size, position and order.

[0014] Base-mediated desilication provides a direct route to generate mesopores (mesoporosity) in high-silica frameworks obtained by steam distillation. (See, for example: Verboekend, D., Milina, M., Mitchell, S. & Perez-Ramirez, J. Hierarchical Zeolites by Desilication: Occurrence and Catalytic Impact of Recrystallization and Restructuring. Crys. Growth Des. 13, 5025-5035 (2013)). In particular, the integration of organic templates during the desilication process has significantly improved crystallinity and mesopores. (See, for example: García-Martínez, J., Johnson, M., Valla, J., Li, K. & Ying, JY Mesostructured Zeolite Y—High Hydrothermal Stability and Superior FCC Catalytic Performance. Catal. Sci. Tech. 2, 987 (2012); Mendoza-Castro, MJ, Serrano, E., Linares, N. & García-Martínez, J. Surfactant-Templated Zeolites: From Thermodynamics to Direct Observation. Adv. Mater. Interfaces 8, 2001 388 (2020)). However, such post-synthetic modification strategies typically lack control over the dissolution and self-assembly processes, resulting in poorly interconnected mesopores. (See, e.g., Schwieger, W. et al. Hierarchy Concepts: Classification and Preparation Strategies for Zeolite Containing Materials with Hierarchical Porosity. Chem. Soc. Rev. 45, 3353-3376, doi: 10.1039 / c5cs00599j (2016)).

[0015] In view of existing attempts to produce hierarchically ordered zeolites, there remains a need in the art for improved synthetic methods. With respect to these and other problems in the art, the present disclosure is directed to providing technical solutions for efficient methods of synthesizing and producing hierarchically ordered zeolites with well-defined long-range mesoporous order. Summary of the invention

[0016] Methods for the synthesis of hierarchically ordered zeolites and zeolite-type materials are provided. Synthetic hierarchically ordered zeolites and zeolite-type materials formed according to the methods herein possess highly well-defined long-range mesoporous order. The methods include base-mediated recombination by dissolving a parent material to the level of oligomeric structural building blocks of the parent material, and minimizing or avoiding amorphization / structural collapse. According to the methods herein, dissolution and self-assembly are fully controlled to produce hierarchically ordered zeolites and zeolite-type materials.

[0017] In some embodiments, a method for the synthesis of a hierarchically ordered crystalline microporous material is provided, whereby the hierarchically ordered crystalline microporous material possesses a high degree of long-range mesoporous order. A matrix crystalline microporous material (CMM) is subjected to dissolution / cleavage into oligomeric components, which are reorganized into a hierarchically ordered mesostructure. An effective amount of the matrix CMM (having an inherent (subsurface, potential, underlying) microporous structure) is combined (merged) with an effective amount of an alkaline agent and an effective amount of a supramolecular template to form an aqueous suspension. The aqueous suspension is hydrothermally treated under conditions effective to form oligomeric units of the matrix CMM, to form shaped micelles of the supramolecular template, and to induce the oligomeric units to assemble around the shaped micelles. The solid is formed into a hierarchically ordered mesostructure having a high degree of long-range mesoporous order, wherein the pores are characterized by retaining the crystalline microporous walls of the inherent microporous structure.

[0018] In some embodiments, a method for the synthesis of hierarchically ordered crystalline microporous materials is provided. The process comprises: forming an aqueous suspension of an effective amount of a parent crystalline microporous material having an inherent microporous structure, an effective amount of an alkaline agent, and an effective amount of a supramolecular template; and hydrothermally treating the aqueous suspension under conditions effective for mesophase transition to dissolve / cleave the parent crystalline microporous material into oligomeric units of the parent crystalline microporous material, form shaped micelles of the supramolecular template, and reorganize the oligomeric units around the shaped micelles into a hierarchically ordered mesostructure.

[0019] In some embodiments, the shape of the micelle is regulated by the selection of the supramolecular template. In some embodiments, the aqueous suspension further comprises an ionic cosolute separated from an anion associated with the supramolecular template, and the shape of the micelle is regulated by the selection of the supramolecular template and the ionic cosolute. In some embodiments, the ionic cosolute is selected from CO32 - 、SO4 2- 、S2O3 2- 、H2PO4 - 、F- , Cl - Br - 、NO3 - ,I - 、ClO4 - 、SCN - and C6H5O8 -3 In some embodiments, the ionic cosolute is selected from SO4 2- 、NO3 - , and ClO4 - In some embodiments, the ionic cosolute comprises NO3 - , and the hierarchically ordered mesoscopic structure has cubic mesophase symmetry. In some embodiments, the ionic cosolute includes SO4 2- , and the hierarchically ordered mesoscopic structure has hexagonal mesophase symmetry. In some embodiments, the ionic cosolute includes ClO4 - , and the hierarchical ordered mesostructure has lamellar mesophase symmetry. In some embodiments, the mesophase transition is characterized by a surfactant packing parameter g, g=V / a0l, where V=total volume of the surfactant tail of the supramolecular template, a0=area of ​​the head group of the supramolecular template, and l=length of the surfactant tail of the supramolecular template. For example: a hierarchical ordered mesostructure with cubic mesophase symmetry may be characterized by a surfactant packing parameter g in the range of about 0.4-0.8; a hierarchical ordered mesostructure with hexagonal mesophase symmetry may be characterized by a surfactant packing parameter g in the range of about 0.4-0.6; and a hierarchical ordered mesostructure with lamellar mesophase symmetry may be characterized by a surfactant packing parameter g in the range of about 0.9-1.1. The amount of ionic co-solute can also be expressed as a molar ratio of supramolecular template to co-solute, for example: a hierarchically ordered mesostructure with cubic mesophase symmetry can be characterized by a molar ratio of supramolecular template to co-solute in the range of about 0.8-1.3; a hierarchically ordered mesostructure with hexagonal mesophase symmetry can be characterized by a molar ratio of supramolecular template to co-solute in the range of about 0.8-1.3; and a hierarchically ordered mesostructure with lamellar mesophase symmetry can be characterized by a molar ratio of supramolecular template to co-solute in the range of about 0.2-0.7.

[0020] In some embodiments, the supramolecular template is a bulky surfactant having one or more dimensions larger than the dimensions of the micropores of the crystalline microporous material to limit diffusion into the micropores of the crystalline microporous material, wherein the dimensions relate to the head group of the surfactant, the tail group of the surfactant, or a co-template. In some embodiments, the supramolecular template contains at least one portion as a head group or a tail group, the portion being selected from organosilanes, hydroxysilyl groups, alkoxysilyl groups, aromatic compounds, branched alkyl groups, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing portions. In some embodiments, the supramolecular template contains at least one cationic portion selected from quaternary ammonium portions and phosphonium portions. In some embodiments, the supramolecular template contains at least one quaternary ammonium group having a terminal alkyl group having 6-24 carbon atoms. In some embodiments, the supramolecular template contains two quaternary ammonium groups, wherein the alkyl group bridging the quaternary ammonium group contains 1-10 carbon atoms. In some embodiments, the supramolecular template contains at least one quaternary ammonium group and at least one head group portion, the head group portion is selected from the group consisting of organosilanes, hydroxysilyl groups, alkoxysilyl groups, aromatic compounds, branched alkyl groups, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing portions. In some embodiments, the supramolecular template contains at least one quaternary ammonium group and at least one head group portion, the head group portion is selected from the group consisting of organosilanes, hydroxysilyl groups, alkoxysilyl groups, aromatic compounds, branched alkyl groups, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing portions, wherein the alkyl group bridging at least one of the quaternary ammonium groups and at least one of the head groups contains 1-10 carbon atoms. In some embodiments, the supramolecular template comprises dimethyloctadecyl(3-trimethoxysilyl-propyl)-ammonium, or a derivative of dimethyloctadecyl(3-trimethoxysilyl-propyl)-ammonium.

[0021] In some embodiments, the alkaline agent is provided in the aqueous suspension at a concentration of about 0.1-5% by weight and is selected from ammonia, ammonium hydroxide and urea. In some embodiments, the alkaline agent is urea, wherein during the hydrothermal treatment, the urea reacts to form ammonium hydroxide, thereby controlling the hydrothermal treatment.

[0022] In some embodiments, the as-formed hierarchically ordered mesostructure is calcined. In some embodiments, the method reduces the amorphous content of the hierarchically ordered mesostructure.

[0023] In some embodiments, the parent CMM comprises a zeolite or a zeolite-type material. In some embodiments, the parent CMM comprises a zeolite having a framework selected from AEI, *BEA, CHA, FAU, MFI, MOR, LTL, LTA and MWW. The parent CMM comprises a zeolite having a FAU framework.

[0024] Any combination of the various embodiments and implementations disclosed herein may be used.These and other aspects and features may be understood from the following description of some embodiments together with the accompanying drawings and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The process of the present disclosure will be described in more detail below and with reference to the accompanying drawings, wherein like reference numerals are used for the same or similar elements.

[0026] Figure 1 and 2 is a schematic overview of the hierarchical order of synthetic pathways through the post-synthetic ensembles described herein.

[0027] Figure 3A depicts the low angle XRD patterns associated with the products synthesized in Examples 1A-1C, and Figure 3B Depicted are high angle XRD patterns associated with the products synthesized in Examples 1A-1C.

[0028] Figure 4A The N2 physical adsorption isotherm is depicted, and Figure 4B Depicted are NLDFT pore size distributions associated with the products synthesized in Examples 1A-1C.

[0029] Figure 5A -C depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example 1B.

[0030] Figure 6 Depicted are SEM images of the products synthesized in Examples 1A-1C.

[0031] Fig. 7A depicts the low angle XRD patterns associated with the products synthesized in Examples 2A-2B, and Figure 7B Depicted are high angle XRD patterns associated with the products synthesized in Examples 2A-2B.

[0032] Fig. 8A The N2 physical adsorption isotherm is depicted, and Figure 8B Depicted are NLDFT pore size distributions associated with the products synthesized in Examples 2A-2B.

[0033] Fig.9A-C depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example 2A.

[0034] Fig. 10A -B depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example 2A, and Fig. 10C Schematic diagram of the unit cell and dimensions of the parent zeolite are depicted.

[0035] Fig.11 Depicted is an electron tomography reconstruction of the hierarchically ordered zeolite synthesized in Example 2B.

[0036] Fig. 12A -C depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example 2B.

[0037] Fig.13A depicts the low angle XRD patterns associated with the products synthesized in Examples 3A-3B, and Fig. 13B Depicted are high angle XRD patterns associated with the products synthesized in Examples 3A-3B.

[0038] Fig.14A The N2 physical adsorption isotherm is depicted, and Fig. 14B Depicted are NLDFT pore size distributions associated with the products synthesized in Examples 3A-3B.

[0039] Fig.15A -E depicts a TEM micrograph of the hierarchically ordered zeolite synthesized in Example 3A.

[0040] Fig.16A -B depicts the low-angle and high-angle XRD patterns associated with the as-made product from Example 4A.

[0041] Fig.17A -C depicts a TEM micrograph of the as-prepared hierarchically ordered zeolite from Example 4A.

[0042] Fig.18 Depicted are FTIR spectra characterizing the acid sites of some embodiments herein.

[0043] Fig.19A -B depicts an NMR spectrum characterizing some of the Examples herein.

[0044] Fig. 20A Depicted are the high-angle XRD patterns of the parent zeolite treated with NH4OH and urea, Fig. 20B The time course of the parent zeolite treated with urea is plotted. Fig. 20C -D depicts the NMR spectrum of the parent zeolite treated with NH4OH and urea, and Fig.20ESchematic representation of zeolite fragments from urea dissolution. DETAILED DESCRIPTION

[0045] Methods for the synthesis of hierarchically ordered zeolites and zeolite-type materials (hereinafter "crystalline microporous materials" or "CMMs", used in the singular or plural as appropriate) are provided. The synthetic hierarchically ordered crystalline microporous materials ("HOCMMs" used in the singular or plural as appropriate) formed according to the methods herein possess highly well-defined long-range mesoporous order. The synthesis of HOCMMs by the process herein overcomes the problems associated with known methods by using base-mediated recombination, by dissolving the parent CMMs to the level of structural building blocks that are oligomers of the parent CMMs, and minimizing or avoiding amorphization / structural collapse. According to the methods herein, CMM dissolution and self-assembly are fully controlled to produce HOCMMs. Compositions formed according to the methods disclosed herein are disclosed in the following co-pending and co-owned U.S. patent application serial numbers: 17 / 857,447, filed on July 5, 2022, entitled “Hierarchically Ordered Crystalline Microporous Materialswith Long-Range Mesoporous Order Having Cubic Symmetry”; 17 / 857,503, filed on July 5, 2022, entitled “Hierarchically Ordered Crystalline Microporous Materials withLong-Range Mesoporous Order Having Hexagonal Symmetry”; and 17 / 857,572, filed on July 5, 2022, entitled “Hierarchically Ordered Crystalline Microporous Materialswith Long-Range Mesoporous Order Having Lamellar Symmetry”, all of which are incorporated herein by reference.

[0046] In some embodiments of the reconstitution: the rate and extent of CMM dissolution are controlled by using urea as an in situ base and by adjusting the hydrothermal temperature to control urea hydrolysis and fine-tuning the pH of the solution; during the initial stage of dissolution, the extent of dissolution into smaller oligomers is controlled by surfactant-CMM interactions, whereby the influence of ion-specific interactions (i.e., the anionic Hofmeister effect (AHE)) on supramolecular self-assembly guides the formation of hierarchically ordered structures with hexagonal mesopore symmetry, bicontinuous gyroid cubic mesopore symmetry, and lamellar symmetry; in some embodiments, the hierarchically ordered structures possess hexagonal P6mm mesopore symmetry, bicontinuous gyroid cubic Ia-3d mesopore symmetry, and lamellar p2 symmetry.

[0047] According to one embodiment of the method, the parent CMM forms an aqueous suspension with an alkaline agent and a supramolecular template agent. In another embodiment, the aqueous suspension includes an ionic cosolute as an additional anion, which is separated from the anion paired with the cation of the supramolecular template. The system is maintained under conditions that induce the parent CMM to cut into oligomeric units of CMM (having only a small portion of monomer units), and induces the hierarchical reorganization of the oligomeric units into mesostructures. Customize system conditions (including crystallization temperature and time), the selection and concentration of supramolecular templates, and the selection and concentration of alkaline agents to control the parent CMM to cut into oligomeric units and control the shape reorganization of those oligomeric units around supramolecular template micelles. Promote the dissolution of the parent CMM to the extent of oligomer formation while minimizing monomer formation, which is controlled by the selection of supramolecular templates, alkaline agents, optional ionic cosolutes, and hydrothermal conditions (including temperature and time). In some embodiments, a substantial portion, a significant portion, or a major portion of the parent CMM is cleaved into oligomeric units, with any remaining portion being in the form of monomeric units or atomic constituents of the CMM. In some embodiments, the size of the oligomeric unit corresponds approximately to the wall thickness of the synthesized mesoporous structure HOCMM. In some embodiments, the interfacial curvature of the micelles and oligomeric units under recombination is adjusted to the desired mesostructure and mesoporosity with the aid of optional ionic cosolutes and the Hoffman effect.

[0048] Under effective crystallization conditions and time, and using effective types of supramolecular templates and alkaline agents in effective relative concentrations, hierarchical ordering occurs through post-synthetic assemblies: the parent CMM is cleaved into oligomeric CMM units, which are rearranged around the shaped micelles formed by the supramolecular template. Hierarchically ordered CMMs with well-defined long-range mesoporous order are formed by a supramolecular template method using surfactant micelles. The mesopore walls are characterized by the parent CMM. Effective supramolecular templates include those supramolecular templates that have one or more properties of forming pores, channels and / or cavities of a size that blocks all, a substantial portion, a significant portion or a major portion of the supramolecular template molecules from entering the parent CMM. These methods disclosed herein achieve base-mediated cleavage of CMM crystals into oligomeric components in the presence of supramolecular templates of the type / characteristics disclosed herein, followed by reorganization of the supramolecular templates around well-defined micelles into hierarchically ordered structures with well-defined long-range mesoporous order.

[0049] The curvature or shape of the micelle results in a final mesophase symmetry, e.g., hexagonal, cubic, or lamellar. The formation of micelles by supramolecular template molecules depends on factors such as supramolecular template type, supramolecular template concentration, presence or absence of ionic cosolutes, CMM type, crystallization temperature, type of alkaline reagent, concentration of alkaline reagent, pH level of the system, and / or presence or absence of other reagents. Typically, at low concentrations, supramolecular templates exist as discrete entities. At higher concentrations, i.e., above the critical micelle concentration (CMC), micelles are formed. Hydrophobic interactions in a system comprising the supramolecular template change the packing shape of the supramolecular template into, e.g., spherical, oblate, or cylindrical micelles, which can then form thermodynamically stable two-dimensional or three-dimensional liquid crystal phases of ordered mesoscopic structures (see, e.g., Zana, R. (ed.). (2005). Dynamics of Surfactant Self-Assemblies: Micelles, Microemulsions, Vesicles and Lyotropic Phases (1st ed.). CRC Press, Chapter 1 of Figure 1 .4, which shows self-assembly based on surfactant and surfactant packing parameters).

[0050] In some embodiments, the Hofmeister Series (HS), ion-specific effects, or lyotropic sequences are followed to select supramolecular templates and / or ionic cosolutes to control the curvature or shape (e.g., spherical, elliptical, cylindrical, or monolayer structure) of the micelles (see, e.g., Beibei Kang, Huicheng Tang, Zengdian Zhao, and Shasha Song. "Hofmeister Series: Insights of Ion Specificityfrom Amphiphilic Assembly and Interface Property” ACS Omega 5(2020):6229-6239). In an embodiment of the method disclosed herein for the synthesis of hierarchically ordered microporous crystalline materials with well-defined long-range mesoporous order, the mesophase transition of the hierarchical assembly produces different mesostructures based on the anion Hofmann effect and supramolecular self-assembly. Anions of different sizes and charges have different polarizabilities, charge densities, and hydration energies in aqueous solution. When paired with positive supramolecular template head groups, these properties can affect the short-range electrostatic repulsion between head groups and the hydration at the micelle interface, thereby changing the area (a0) of the head group. Such ion-specific interactions can be the driving force for changing the micelle curvature and inducing mesophase transitions. Based on HS(SO4 2- >HPO4 2- >Oac - >Cl - >Br - >NO3 - >ClO4 - >SCN - ), strongly hydrated ions (left side of HS) can increase the micelle curvature, while weakly hydrated ions can decrease the micelle curvature. The surfactant packing parameter g = V / a0l (V = total volume of the surfactant tail, a0 = area of ​​the head group, l = length of the surfactant tail) can be used to describe these intermediate phase transitions.

[0051] In the methods disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, suitable alkaline agents include one or more alkaline compounds to maintain the system at a pH level greater than about 8. In some embodiments, the alkaline agent is provided in an aqueous suspension at a concentration of about 0.1-2.0 M. In some embodiments, the alkaline agent is provided in an aqueous suspension at a concentration of about 0.1-5 wt %. In some embodiments, the alkaline agent includes urea. In some embodiments, the alkaline agent includes ammonia. In some embodiments, the alkaline agent includes ammonium hydroxide. In some embodiments, the alkaline agent includes sodium hydroxide. In some embodiments, the alkaline agent includes an alkali metal hydroxide, including hydroxides of sodium, lithium, potassium, rubidium, or cesium.

[0052] In some embodiments, the alkaline agent is effective to achieve controlled hydrolysis; for example, urea can be used as an alkaline agent, and during the hydrolysis, urea reacts to form ammonium hydroxide. For example, a higher urea concentration can be used in the initial step, and the alkalinity can be maintained by gradual urea hydrolysis. In such an embodiment, the pH increases relatively slowly to a maximum pH as a function of time, which is beneficial to the process, rather than adding a certain amount of another alkaline agent such as ammonium hydroxide to the maximum pH in the initial solution. Unlike conventional bases that act quickly, urea is pH neutral under ambient conditions and can be evenly dispersed throughout the zeolite micropores without affecting them.

[0053] In some embodiments, the alkaline reagent comprises a compound having the general formula R X H 4-X N + [A - ] alkylammonium cation, wherein X = 1-4, and R1, R2, R3 and R4 can be the same or different C1-C30 alkyl groups, and wherein [A - ] is the counter anion, which can be OH - Br - , Cl - or I - In some embodiments, the alkaline agent comprises a quaternary ammonium cation having an alkoxysilyl group, a phosphonium group, an alkyl group having a bulky substituent, or an alkoxy group having a bulky substituent. In some embodiments, the alkylammonium cation used in this regard acts as a base rather than as a surfactant or template.

[0054] In some embodiments using ammonia, ammonium hydroxide or an alkali metal hydroxide, amorphous material is also present in the product along with the crystalline material. In some embodiments, upon calcining the as-prepared HOCMM, the amount of apparent amorphous material present (e.g., overall broad band at 25° (2θ) in XRD) is reduced, indicating apparent "self-healing" after calcination. In some embodiments, by controlled hydrolysis of urea to ammonium hydroxide, the amount of apparent amorphous material present in HOCMM (e.g., overall broad band at 25° (2θ) in XRD) is reduced when compared to alternative pathways such as NaOH or direct use of ammonium hydroxide.

[0055] In the method disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, a suitable surfactant is provided as a supramolecular template to assist the reorganization and recrystallization of dissolved components (oligomers) through covalent and / or electrovalent interactions. The supramolecular template is provided in an aqueous suspension at a concentration of about 0.01-0.5M. In some embodiments, the suitable supramolecular template is provided in an aqueous suspension at a concentration of about 0.5-10 wt%. Suitable supramolecular templates are characterized by restricted diffusion within the microporous channels of the parent CMM, referred to as bulky surfactants or bulky supramolecular templates. The diffusion of supramolecular template molecules into micropore-channels or cavities promotes CMM dissolution. This is minimized in the top-down method disclosed herein for the synthesis of hierarchically ordered CMMs with well-defined long-range mesoporous order, wherein the effective supramolecular template minimizes its diffusion or partial diffusion into the CMM pore channels, cavities or window openings. Such supramolecular templates have a suitable size to block such diffusion. The appropriate size may be based on the size of the head group and / or tail group of the supramolecular template. In some embodiments, the appropriate size may be based on a co-template having one or more components with appropriate head and / or tail groups, or a template system arranged in such a way as to minimize or prevent diffusion into the CMM pore channels, cavities or window openings. By minimizing the diffusion of the template into the CMM pore channels, the dissolution of the CMM into oligomers and the overall reorganization and assembly of the hierarchically ordered CMMs with well-defined long-range mesoporous order disclosed herein are promoted. In some embodiments, the supramolecular template is a template in which at least a substantial portion, a significant portion or a major portion of the surfactant does not enter the pores and / or channels of the CMM. For example, compared to quaternary ammonium surfactants including hexadecyltrimethylammonium bromide (CTAB) (~0.25nm) without such bulky groups, organosilanes (~0.7nm) are relatively large. In some embodiments, the supramolecular template contains long-chain linear groups (>~0.6nm). In some embodiments, the supramolecular template contains aromatic or aromatic derivative groups (>~0.6nm). In some embodiments, the supramolecular template contains one or more bulky groups having dimensions based on modeling the molecular size as a cuboid with dimensions A, B, and C using the van der Waals radii of each atom, wherein one or more, two or more, or all three of the dimensions A, B, and C are sufficiently close in size, or sufficiently large in size, to restrict diffusion into the micropores of the selected parent CMM.

[0056] In some embodiments, the effective surfactant as a supramolecular template contains at least one part as a head group or a tail group, and the part is selected from an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound (aromatic), a branched alkyl group, a sulfonate group, a carboxylate group, a phosphate group, and a combination including one of the foregoing parts. In some embodiments, the effective supramolecular template is an organosilane containing at least one hydroxysilyl group as a head group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one hydroxysilyl group as a tail group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one alkoxysilyl group as a head group part. In some embodiments, the effective supramolecular template is an organosilane containing at least one alkoxysilyl group as a tail group part. In some embodiments, the effective supramolecular template contains at least one aromatic compound as a head group part. In some embodiments, the effective supramolecular template contains at least one aromatic compound as a tail group part. In some embodiments, the effective supramolecular template contains at least one branched alkyl group as a head group part. In some embodiments, the effective supramolecular template contains at least one branched alkyl group as a tail group part. In some embodiments, the effective supramolecular template contains at least one sulfonate as a head group portion. In some embodiments, the effective supramolecular template contains at least one sulfonate as a tail group portion. In some embodiments, the effective supramolecular template contains at least one carboxylate as a head group portion. In some embodiments, the effective supramolecular template contains at least one carboxylate as a tail group portion. In some embodiments, the effective supramolecular template contains at least one phosphate as a head group portion. In some embodiments, the effective supramolecular template contains at least one phosphate as a tail group portion. These portions are characterized by one or more dimensions that limit diffusion into the pores of the parent CMM. In some embodiments, where the CMM is characterized by pores of various sizes, the selected portions are characterized by one or more dimensions that limit diffusion into the largest pores of the parent CMM.

[0057] In some embodiments, the effective supramolecular template contains at least one cationic part. In some embodiments, the effective supramolecular template contains at least one cationic part selected from a quaternary ammonium part and a phosphonium part. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group having a terminal alkyl group having 6-24 carbon atoms. In some embodiments, the effective supramolecular template contains two quaternary ammonium groups, wherein the alkyl group bridging the quaternary ammonium group contains 1-10 carbon atoms. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group and at least one constituent group - the head group part as described above. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group and at least one constituent group - the tail group part as described above. In some embodiments, the effective supramolecular template contains at least one quaternary ammonium group, at least one constituent group - the head group part as described above, and an alkyl group containing 1-10 carbon atoms bridging at least one of the quaternary ammonium groups and at least one of the head groups. In some embodiments, an effective supramolecular template contains at least one quaternary ammonium group, at least one constituent group - a tail group portion as described above, and an alkyl group containing 1-10 carbon atoms bridging at least one of the quaternary ammonium groups and at least one of the tail groups.

[0058] In some embodiments, the effective supramolecular template comprises a quaternary ammonium compound and a constituent group comprising one or more bulky organosilane or alkoxysilyl substituents. In some embodiments, the effective supramolecular template comprises a quaternary ammonium compound and a constituent group comprising one or more long-chain organosilane or alkoxysilyl substituents. In some embodiments, the effective supramolecular template cation comprises dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium or a derivative of dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium. In some embodiments, the effective supramolecular template cation comprises dimethylhexadecyl (3-trimethoxysilyl-propyl)-ammonium or a derivative of dimethylhexadecyl (3-trimethoxysilyl-propyl)-ammonium. In some embodiments, effective supramolecular template cations include bisacyloxy amphiphilic organosilanes such as [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium or derivatives of [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium.

[0059] In some embodiments, an effective supramolecular template comprises a quaternary phosphonium compound and a constituent group comprising one or more bulky aromatic substituents. In some embodiments, an effective supramolecular template comprises a quaternary phosphonium compound and a constituent group comprising one or more bulky alkoxysilyl or organosilane substituents.

[0060] In some embodiments, the effective supramolecular template contains a tail group portion selected from the following: an aromatic group containing 6-50, 6-25, 10-50 or 10-25 carbon atoms, an alkyl group containing 1-50, 1-25, 5-50, 5-25, 10-50 or 10-25 carbon atoms, an aryl group containing 1-50, 1-25, 5-50, 5-25, 10-50 or 10-25 carbon atoms, or a combination of aromatic and alkyl groups with up to 50 carbon atoms. In some embodiments, the effective supramolecular template contains a head group moiety selected from the group consisting of an aromatic group containing 6-50, 6-25, 10-50, or 10-25 carbon atoms, an alkyl group containing 1-50, 1-25, 5-50, 5-25, 10-50, or 10-25 carbon atoms, an aryl group containing 1-50, 1-25, 5-50, 5-25, 10-50, or 10-25 carbon atoms, or a combination of aromatic and alkyl groups having up to 50 carbon atoms. In some embodiments, the effective supramolecular template contains a co-templating agent selected from the group consisting of quaternary ammonium compounds (including, for example, quaternary alkylammonium cationic species) and quaternary phosphonium compounds.

[0061] In some embodiments, the effective supramolecular template includes (a) at least one of the following: an aromatic quaternary ammonium compound, a branched alkyl chain quaternary ammonium compound, an alkylbenzene sulfonate (salt), an alkylbenzene phosphonate (salt), an alkylbenzene carboxylate (salt), or a substituted phosphonium cation; and (b1) and as a head group, a constituent group including at least one of an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound, a branched alkyl group, a sulfonate group, a carboxylate group, or a phosphate group; or (b2) and as a tail group, a constituent group including at least one of an organosilane, a hydroxysilyl group, an alkoxysilyl group, an aromatic compound, a branched alkyl group, a sulfonate group, a carboxylate group, or a phosphate group. In some embodiments, the effective supramolecular template includes a sulfonate group (a non-limiting example is sulfonated bis(2-hydroxy-5-dodecylphenyl)methane (SBHDM)). In some embodiments, the effective supramolecular template includes a carboxylate group (a non-limiting example is sodium 4-(octyloxy)benzoate). In some embodiments, effective supramolecular templates include phosphonate groups (a non-limiting example is tetradecyl (1,4-phenyl) diphosphonate). In some embodiments, effective supramolecular templates include aromatic groups (a non-limiting example is benzyl hexadecyl dimethyl ammonium chloride). In some embodiments, effective supramolecular templates include aliphatic groups (a non-limiting example is tetraoctyl ammonium chloride).

[0062] The supramolecular template is provided as a cation / anion pair. In some embodiments, the cation of the supramolecular template is as described above, and is selected from, for example, Cl - Br – OH – 、F – and I – In some embodiments, the cation of the supramolecular template is as described above, and is paired with an anion such as Cl - Br – or OH – Pairing. In some embodiments, the effective supramolecular template includes dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (commonly abbreviated as "TPOAC") or a derivative of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. In some embodiments, the effective supramolecular template includes dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride or a derivative of dimethylhexadecyl[3-(trimethoxysilyl)propyl]ammonium chloride. In some embodiments, the effective supramolecular template includes [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium iodide or a derivative of [2,3-bis(dodecanoyloxy)-propyl](3-(trimethoxysilyl)propyl)-dimethylammonium iodide.

[0063] In some embodiments, the system includes an effective amount of an ionic cosolute (i.e., in addition to the anion paired with the supramolecular template). In some embodiments where an ionic cosolute is used, it is provided at a concentration of about 0.01-0.5 M in the aqueous suspension. In some embodiments where an ionic cosolute is used, it is provided at a concentration of about 0.01-5 wt % in the aqueous suspension. In some embodiments, the ionic cosolute is selected from CO3 2- 、SO4 2- 、S2O3 2- 、H2PO4 - 、F - , Cl - Br - 、NO3 - ,I - 、ClO4 - 、SCN - and C6H5O8 -3 (citrate). In some embodiments, the ionic cosolute is selected from SO4 2- 、NO3 - and ClO4 - In some embodiments, the ionic cosolute is selected based on the Hofmann series / lyotropic series to control the curvature / shape of the micelle to produce a desired mesophase symmetry, such as hexagonal, cubic, or lamellar. In some embodiments, nitrate (NO3 - ) is an ionic cosolute selected based on the Hofmann series / lyotropic ion series to control the curvature / shape of the micelles to produce a hierarchically ordered CMM with well-defined long-range mesoporous order, which has cubic mesophase symmetry; in some embodiments using nitrate as the ionic cosolute, a nitrate such as ammonium nitrate or a metal nitrate is used, wherein the metal can be an alkali metal, an alkaline earth metal, a transition metal, a noble metal, or a rare earth metal. In some embodiments, sulfate (SO4 2- ) is an ionic cosolute selected based on the Hofmann series / lyotropic ion series to control the curvature / shape of the micelles to produce hierarchically ordered CMMs with well-defined long-range mesoporous order, which possess hexagonal mesophase symmetry; in some embodiments using sulfate as the ionic cosolute, sulfate salts such as ammonium sulfate or metal sulfates are used, wherein the metal can be an alkali metal, an alkaline earth metal, a transition metal, a noble metal, or a rare earth metal. In some embodiments, perchlorate (ClO4 -) is an ionic co-solute selected based on the Hofmann series / lyotropic ion series to control the curvature / shape of the micelles to produce a hierarchically ordered CMM with well-defined long-range mesoporous order, which possesses lamellar mesophase symmetry; in some embodiments using perchlorate as the ionic co-solute, a sulfate, such as sodium perchlorate, or another metal perchlorate is used, wherein the metal can be an alkali metal, an alkaline earth metal, a transition metal, a noble metal, or a rare earth metal.

[0064] The present disclosure is applicable to various types of CMMs as matrix materials, including zeolites or zeolite-type materials. In some embodiments, the matrix CMM exhibits good crystallinity and Al distribution to obtain high quality HOCMMs while minimizing complex phases and / or impurities.

[0065] The CMM system is designed to be used in the field of cleaning and maintenance. Read more: ABW, ACO, AEI, AEL, AEN AET、AFG、AFI、AFN、AFO、AFR、AFS、AFT、AFV、AFX、AFY、AHT、ANA、ANO、APC、APD AST、ASV、ATN、ATO、ATS、ATT、ATV、AVE、AVL、AWO、AWW、BCT、BEC、BIK、BOF、B OG、BOZ、BPH、BRE、BSV、CAN、CAS、CDO、CFI、CGF、CGS、CHA、-CHI、-CLO、CON、CS V、CZP、DAC、DDR、DFO、DFT、DOH、DON、EAB、EDI、EEI、EMT、EON、EPI、ERI、ESV、 ETL、ETR、ETV、EUO、EWO、EWS、EZT、FAR、FAU、FER、FRA、GIS、GIU、GME、GON、GOO HEU、IFO、IFR、-IFT、-IFU、IFW、IFY、IHW、IMF、IRN、IRR、-IRY、ISV、ITE、IT G、ITH、ITR、ITT、-ITV、ITW、IWR、IWS、IWV、IWW、JBW、JNT、JOZ、JRY、JSN、JSR、 JST、JSW、KFI、LAU、LEV、LIO、-LIT、LOS、LOV、LTA、LTF、LTJ、LTL、LTN、MAR、M AZ、MEI、MEL、MEP、MER、MFI、MFS、MON、MOR、MOZ、MRT、MSE、MSO、MTF、MTN、MTT、 MTW、MVY、MWF、MWW、NAB、NAT、NES、NON、NPO、NPT、NSI、OBW、OFF、OKO、OSI、OS O、OWE、-PAR、PAU、PCR、PHI、PON、POR、POS、PSI、PTO、PTT、PTY、PUN、PWN、PWO、 PWW、RHO、-RON、RRO、RSN、RTE、RTH、RUT、RWR、RWY、SAF、SAO、SAS、SAT、SAV、S BE、SBN、SBS、SBT、SEW、SFE、SFF、SFG、SFH、SFN、SFO、SFS、SFW、SGT、SIV、SOD、 SOF、SOR、SOS、SOV、SSF、SSY、STF、STI、STT、STW、-SVR、SVV、SWY、-SYT、SZR、T ER、THO、TOL、TON、TSC、TUN、UEI、UFI、UOS、UOV、UOZ、USI、UTL、UWY、VET、VFI、VNI, VSV, WEI, -WEN, YFI, YUG, ZON, *BEA, *CTH, *-EWT, *-ITN, *MRE, *PCS, *SFV, *-SSO, *STO, *-SVY and *UOE. For example, some zeolites known to be useful in the petroleum refining industry include, but are not limited to, AEI, *BEA, CHA, FAU, MFI, MOR, LTL, LTA or MWW. In some embodiments, the parent zeolite may be a (FAU) framework zeolite comprising USY, for example, having a micropore size associated with a 12-membered ring of, when viewed along the

[111] direction, In some embodiments, the parent zeolite may be a (MFI) framework zeolite including ZSM-5, for example, having micropore sizes associated with the 10-membered ring when viewed along the

[100] and

[010] directions of and In some embodiments, the parent zeolite may be a (MOR) framework zeolite, which includes mordenite, for example, having pore sizes associated with 12-membered rings and 8-membered rings, respectively, when viewed along the

[001] and

[001] directions. and In some embodiments, the parent zeolite may be a (*BEA) framework zeolite including zeolite beta polymorph A, for example having pore sizes associated with the 12-membered ring when viewed along the

[100] and

[001] directions of and In some embodiments, the parent zeolite may be a (CHA) framework zeolite, which includes a chabazite zeolite, for example, having a pore size associated with the 8-membered ring when viewed orthogonally to the

[001] direction of In some embodiments, the parent zeolite may be a (LTL) framework zeolite, which includes a Linde L-type zeolite (zeolite L), for example, having a pore size associated with the 12-membered ring of In some embodiments, the parent zeolite may be a (LTA) framework zeolite, which includes a Linde A-type zeolite (zeolite A), for example, having a pore size associated with an 8-membered ring of In some embodiments, the parent zeolite may be an (AEI) framework zeolite, for example, having a pore size associated with the 8-membered ring of In some embodiments, the parent zeolite may be a (MWW) framework zeolite comprising MCM-22, for example, having micropore sizes associated with the 10-membered ring when viewed "between layers" and "within layers" orthogonal to the

[001] direction, respectively. and

[0066] In some embodiments, the parent CMM is a zeolitic material, such as aluminophosphate (AlPO), silicon-substituted aluminophosphate (SAPO), or metal-containing aluminophosphate (MAPO). In some embodiments, the parent CMM is a zeolitic siliceous framework material only.

[0067] As described above, embodiments herein include supramolecular templates containing one or more bulky groups having dimensions based on modeling the molecular dimensions as a cuboid having dimensions A, B, and C using the van der Waals radius of each atom, wherein one or more, two or more, or all three of dimensions A, B, and C are sufficiently close in size, or sufficiently large in size, to restrict diffusion into the micropores of the CMM. Also as described above with respect to known parameters associated with the pore size of exemplary zeolites, such parameters affect the selection of supramolecular templates. For example, in the examples herein, FAU zeolite was used; when the supramolecular template material was CTAB (~0.25 nm), HOCMM was not achieved; however, when the supramolecular template was an organosilane (~0.7 nm), HOCMM was achieved because these were closer in size to the pore size of the FAU zeolite and were therefore restricted from entering such pores. Likewise, suitable supramolecular templates are determined based on the selected parent CMM.

[0068] In some embodiments, the parent CMM used in the method is a zeolite herein having a SAR suitable for a particular type of zeolite. Typically, the SAR of the parent zeolite may be in the following ranges: about 2-10000, 2-5000, 2-500, 2-100, 2-80, 5-10000, 5-5000, 5-500, 5-100, 5-80, 10-10000, 10-5000, 10-500, 10-100, 10-80, 50-10000, 50-5000, 50-100, 50-500 or 50-100. In some embodiments, the SAR of the parent zeolite is greater than or equal to 5 or 10 to achieve long-range order. In embodiments with a SAR of less than 10, uniform mesopores and a certain degree of order may be obtained, and amorphous framework material is retained in the product.

[0069] Synthesis steps

[0070] Figure 1 and 2 A schematic overview of the hierarchical order of the synthetic pathways through the post-synthesis ensemble described herein is provided, including the overall synthetic mechanism and how the AHE affects the g value to change the micelle curvature and induce the mesophase transition. Figure 1 and 2The CMM schematically depicted in is a FAU zeolite, but it is understood that other CMMs may be used as the parent CMM via a post-synthesis assembly synthesis route.

[0071] The method comprises base-mediated dissolution / cleavage of a parent CMM into oligomeric components and reorganization into hierarchically ordered mesostructures by supramolecular templating and, in some embodiments, by the Hofmann effect. The parent CMM 10 is provided in a crystalline form. An effective amount of an alkaline agent for supramolecular templating and an effective amount of a surfactant are added to form an aqueous suspension, and the suspension is maintained under hydrothermal conditions to form oligomeric CMM units 12 of the parent CMM (e.g., oligomeric zeolite units when the parent CMM is a zeolite). The supramolecular template molecules 14 form shaped micelles 16 ( Figure 2 ), and the oligomeric CMM units are hierarchically reorganized around the shaped micelles and crystallized into an ordered mesostructure HOCMM 18, HOCMM 18 having mesopores 20 of defined symmetry and mesopore walls formed by the oligomeric CMM units, thereby retaining the micropores 22 of the inherent CMM structure of the parent CMM. In some embodiments, the material composition (composition) produced by the method herein is HOCMM 18 containing shaped micelles 16. In some embodiments, the material composition produced herein is HOCMM 18, which removes the surfactant 14 formed into the shaped micelles 16, for example, by: a chemical method, such as solvent extraction, chemical oxidation or ionic liquid treatment; or a physical method such as calcination, supercritical CO2, microwave-assisted treatment, ultrasound-assisted treatment, ozone treatment or plasma technology.

[0072] Different mesophase transitions that produce hierarchical ensembles of different mesostructures can be attributed to the synergistic effect of anionic Hofmann effects (ion-specific interactions) in supramolecular self-assembly. Anions of different sizes and charges have different polarizabilities, charge densities, and hydration energies in aqueous solution. When paired with positive surfactant head groups, these properties can affect the electrostatic repulsion between head groups and the hydration at the micelle interface, thereby changing the area (a0) of the head groups. Such short-range ion-specific interactions can be a significant driving force for changing the micelle curvature and inducing mesophase transitions.

[0073] refer to Figure 2, showing the overall synthesis mechanism, including a schematic diagram of how AHE affects g value to change the micelle curvature and induce mesophase transition. The molar ratio of surfactant (also referred to herein as supramolecular template) to cosolute (which can be expressed as the molar ratio of surfactant to salt) effectively produces the desired mesoporous structure. The molar ratio of surfactant to cosolute is selected to produce a surfactant filling parameter suitable for inducing mesophase transition to the desired geometry, thereby inducing a change in micelle curvature. For example, when sulfate is used as an ionic cosolute, the micelle curvature is represented by a surfactant filling parameter g of about 1 / 2, or about 0.4-0.6, or 0.5, and the resulting HOCMM has a long-range mesoporous order of hexagonal symmetry. When nitrate is used as an ionic cosolute, the micelle curvature is represented by a surfactant filling parameter g in the range of about 1 / 2 to about 2 / 3, or about 0.4-0.8, 0.4-0.67, 0.5-0.8 or 0.5-0.67, and the resulting HOCMM has a long-range mesoporous order of cubic symmetry. When perchlorate is used as an ionic co-solute, the micelle curvature is represented by a surfactant packing parameter g in the range of about 0.9-1.1 or 1, and the resulting HOCMM has a long-range mesoporous order with lamellar symmetry. For example, in some embodiments, the molar ratio of surfactant to co-solute for the synthesis of HOCMMs with long-range mesoporous order with hexagonal symmetry can be in the range of about 0.8-1.3, 0.9-1.3, 0.9-12, or 0.8-1.2. For example, in some embodiments, the molar ratio of surfactant to co-solute for the synthesis of HOCMMs with long-range mesoporous order with cubic symmetry can be in the range of about 0.8-1.3, 0.9-1.3, 0.9-12, or 0.8-1.2. For example, in some embodiments, the molar ratio of surfactant to co-solute for the synthesis of HOCMMs with long-range mesoporous order with lamellar symmetry can be in the range of about 0.2-0.7, 0.3-0.7, 0.2-0.6, or 0.3-0.6. It is understood that, as described herein, wider ranges can be applied and these ranges can vary depending on the selected surfactant and co-solute, which affect the values ​​of V (total volume of the surfactant tail), a0 (area of ​​the head group), and l (length of the surfactant tail) to determine g (surfactant packing parameter). In some embodiments, the range of surfactant packing parameter g and / or the range of surfactant to co-solute molar ratio is effective for organosilane supramolecular templates such as dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium or derivatives of dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium.

[0074] Figure 2The effect of ion-specific interactions (Hofmann effect) on the curvature of micelles during self-assembly is also shown. Anions of different sizes and charges have different polarizabilities, charge densities, and hydration energies in aqueous solution. When paired with positive surfactant head groups, these properties can affect the electrostatic repulsion between the head groups and the hydration at the micelle interface, thereby changing the area (a0) of the head groups. Such short-range ion-specific interactions can be a significant driving force for changing the curvature of the micelles and inducing mesophase transitions. Based on the Hofmann series (SO4 2- >HPO4 2- >Oac - >Cl - >Br - >NO3 - >ClO4 - >SCN - ), strongly hydrated ions (left side of the series) can increase the micelle curvature, while weakly hydrated ions can reduce the micelle curvature. Although not wishing to be bound by theory, the effect of co-solutes such as salts in the mesophase order can be attributed to their charge balancing effect; in surfactant self-assembly, high density of surfactant molecules are tightly packed into micelles due to hydrophobic effects; as a result, the electrostatic repulsion of the charged head groups should be minimized by counter anions to induce easy aggregation; therefore, although the concentration of the poly(anionic) zeolite component is gradually changed, the auxiliary counter anions play a role in stabilizing the micelles.

[0075] An effective amount of solvent is used in this process. In some embodiments, the solvent is water. In some embodiments, in the presence of a co-solvent selected from a polar solvent, a non-polar solvent, and a pore swelling agent (e.g., 1,3,5-trimethylbenzene), the solvent is water. In some embodiments, in the absence of water, the solvent is selected from a polar solvent, a non-polar solvent, and a pore swelling agent (e.g., 1,3,5-trimethylbenzene). In some embodiments, before heating, the mixture components are added to the reaction vessel together with water. Typically, water allows sufficient mixing to achieve a more uniform distribution of the suspension components, which ultimately produces a more desirable product because each crystal is more closely matched to the next crystal in nature. Inadequate mixing may result in undesirable products or a lower degree of long-range order about the amorphous phase.

[0076] The suspension components are combined in any suitable order and mixed thoroughly to form a uniform distribution of the suspension components. The suspension can be maintained in an autoclave under autogenous pressure (either from the components or from the components plus a gas purge added to the container prior to heating), or in another suitable container, under agitation, such as by stirring, tumbling and / or shaking. The mixing of the suspension components is carried out at about 20-60° C., 20-50° C., or 20-40° C.

[0077] The steps of cleavage and reassembly occur during the hydrothermal treatment to form a solid (product, HOCMM with well-defined long-range mesoporous order) suspended in a supernatant (mother liquor). The hydrothermal treatment is performed for a period of about 4-168, 12-168, 24-168, 4-96, 12-96, or 24-96 hours; at a temperature of about 70-250, 70-210, 70-180, 70-160, 70-150, 90-250, 90-210, 90-180, 90-160, 90-150, 110-250, 110-210, 110-180, 110-160, or 110-150°C; and at a pressure of about atmospheric pressure to autogenous pressure. In some embodiments, the hydrothermal treatment occurs in the same container as the container used for mixing, or the suspension is transferred to another container (e.g., another autoclave or low pressure vessel). In some embodiments, the container for the hydrothermal treatment is static. In some embodiments, the container for the hydrothermal treatment is under stirring sufficient to suspend the components.

[0078] HOCMM with well-defined long-range mesoporous order is the recovered product. The solid is recovered using known techniques such as centrifugation, decantation, gravity, vacuum filtration, filter press or drum. The recovered HOCMM with well-defined long-range mesoporous order is dried, for example, at a temperature of about 50-150, 50-120, 80-150 or 80-120° C., at atmospheric pressure or under vacuum conditions, for a period of about 0.5-96, 12-96 or 24-96 hours.

[0079] In some embodiments, the dried HOCMM having well-defined long-range mesoporous order is calcined, for example to remove the supramolecular templates retained in the mesopores and other components from the mesopores and / or the discrete zeolite unit cell micropores. In embodiments where calcination is performed, the conditions for calcination may include a temperature in the range of about 350-650, 350-600, 350-550, 500-650, 500-600, or 500-550° C., atmospheric pressure or under vacuum, and a time period of about 2.5-24, 2.5-12, 5-24, or 5-12 hours. Calcination may occur at a heating rate in the range of about 0.1-10, 0.1-5, 0.1-3, 1-10, 1-5, or 1-3° C. / minute. In some embodiments, calcination may have a first step of ramping to a temperature of about 100-150° C., holding for about 1.5-6 or 1-12 hours (at a ramp rate of about 0.1-5, 0.1-3, 1-5, or 1-3° C. / minute), then ramping to a higher temperature with a final hold time in the range of about 1.5-6 or 1-12 hours.

[0080] In some embodiments, the supernatant remaining after the product is collected from the system is collected, and all or part of it can be reused as all or part of the solution in the subsequent process of the synthesis of HOCMM with well-defined long-range mesoporous order. In this embodiment, the collected supernatant used in the subsequent process is referred to as the supernatant from the previous synthesis. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary alkaline reagent (such as urea). In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary supramolecular template. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary ionic cosolutes. In some embodiments, a new synthesis can occur with the supernatant from the previous synthesis and the parent CMM and an additional amount of supplementary alkaline reagent (such as urea) and / or supplementary supramolecular templates and / or optional supplementary ionic cosolutes.

[0081] product

[0082] The collected compositions of matter as described herein are hierarchically ordered CMMs (e.g., zeolites) with well-defined long-range mesoporous orderliness. These are characterized by defined mesoporous channel directions with zeolite microporous channels in the walls of the mesostructure. The HOCMMs collected from the synthesis process with well-defined long-range mesoporous orderliness have supramolecular templates as described herein in the mesopores (i.e., before calcining or extracting the supramolecular template). In some embodiments, the HOCMMs collected from the synthesis process with well-defined long-range mesoporous orderliness have micelles of supramolecular templates as described herein in the mesopores (i.e., before calcining or extracting the supramolecular template). The collected compositions of matter as described herein retain the structural integrity of the microporous zeolite structure by: controlled cutting of the parent zeolite, followed by controlled reorganization of the zeolite oligomers under controlled micelle curvature to produce HOCMMs with defined mesoporous symmetry.

[0083] This well-defined long-range mesopore is elusive in the field of hierarchically ordered zeolites. Long-range order is defined by secondary peaks associated with the periodic arrangement of mesopores in the x-ray diffraction (XRD) diagram of a given mesophase, and / or by observation in a microscope, as demonstrated in the embodiments herein. These peaks associated with the mesoporous properties of the product are observed at low 2θ angles. The material also exhibits high-angle peaks associated with zeolites and is observed at high 2θ angles. In some embodiments, low-angle peaks refer to those occurring at 2θ angles less than about 6 °.

[0084] In some embodiments herein, the long-range mesoporous order of the HOCMMs produced according to the methods described herein is characterized by a mesopore periodicity that repeats over a length greater than about 50 nm.

[0085] In some embodiments herein, the HOCMM produced according to the methods described herein is a cubic mesophase having Ia-3d symmetry, and the long-range mesoporous order is characterized by the presence of secondary XRD peaks associated with the periodic arrangement of the mesopores at one or more of the (220), (321), (400), (420), and (332) reflections. In some embodiments herein, the HOCMM produced according to the methods described herein is a hexagonal mesophase having p6mm symmetry, and the long-range mesoporous order is characterized by the presence of secondary peaks at the (11) and / or (20) reflections in the XRD. In some embodiments herein, the HOCMM produced according to the methods described herein is a lamellar mesophase having p2 symmetry, and the long-range mesoporous order is characterized by the presence of a secondary peak at the (200) reflection in the XRD.

[0086] In some embodiments herein, the HOCMMs having well-defined long-range mesoporous order produced according to the methods described herein have a pore size of about 200-1500, 200-1000, 200-900, 400-1500, 400-1000, 400-900, 500-1500, 500-1000, or 500-900 m 2 / g of surface area. In embodiments herein, the HOCMMs produced according to the methods described herein with well-defined long-range mesoporous order have mesopore diameters of about 2-50, 2-20, or 2-10 nm. In embodiments herein, the HOCMMs produced according to the methods described herein with well-defined long-range mesoporous order have a ratio of silica to alumina of about 2.5-1500, 3-1500, 4-1500, 5-1500, 6-1500, 2.5-1000, 3-1000, 4-1000, 5-1000, 6-1000, 2.5-500, 3-500, 4-500, 5-500, 6-500, 2.5-100, 3-100, 4-100, 5-100, or 6-100. In embodiments described herein, the HOCMMs having well-defined long-range mesoporous order produced according to the methods described herein have a total pore volume of about 0.01-1.50, 0.01-1.0, 0.01-0.75, 0.01-0.65, 0.1-1.50, 0.1-1.0, 0.1-0.75, 0.1-0.65, 0.2-1.50, 0.2-1.0, 0.2-0.75, 0.2-0.65, 0.3-1.50, 0.3-1.0, 0.3-0.75, or 0.3-0.65 cc / g.

[0087] In embodiments herein, the product produced by the above method and demonstrated in the examples herein is characterized by a mesophase with cubic symmetry. In some embodiments, the product is a 3D-cubic ordered mesoporous zeolite. The HOCMM with a mesophase with cubic symmetry is characterized by a cubic mesoporous channel orientation, wherein the CMM microporous channels are in the walls of the mesostructure. The cubic mesophase may have one of Ia-3d, Fm-3m, Pm-3n, Pn-3m or Im-3m symmetry. In embodiments herein, the cubic mesophase has Ia-3d symmetry, and the secondary XRD peaks associated with the periodic arrangement of the mesopores are present at one or more of the (220), (321), (400), (420) and (332) reflections. In embodiments herein, the cubic mesophase has Ia-3d symmetry, and a high degree of long-range cubic mesophase order can be observed microscopically by electron beam observation along a suitable zone axis (e.g.,

[311] ,

[111] , or

[110] zone axis). In embodiments herein, nitrate (NO3 -) is used as an ionic co-solute to produce a mesophase with cubic symmetry. In these embodiments, the CMM structure is arranged with cubic symmetry on the mesoscale, wherein the CMM particles (regardless of their atomic level symmetry or structure) are arranged around micelles (on the mesoscale), and thereby the micelles are arranged to exhibit cubic symmetry. Therefore, HOCMMs with a cubic mesophase include CMMs characterized by atomic level symmetry and having micropores inherent to that type of CMM, which are arranged with cubic symmetry on the mesoscale level with mesopores, wherein the walls of the mesopores and a large amount of mesostructure between the mesopores are characterized by the CMM (e.g., crystalline zeolites). This is produced as described herein by forming oligomers of the intrinsic CMM and arranging those oligomers around micelles exhibiting cubic symmetry on the mesoscale. In one embodiment, a HOCMM is provided that includes an MFI zeolite having an atomic level orthorhombic symmetry arranged at a mesoscale with a cubic symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MFI zeolite, oligomers of the parent MFI zeolite form and arrange around micelles that exhibit cubic symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a CHA zeolite having an atomic level trigonal symmetry arranged at a mesoscale with a cubic symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent CHA zeolite, oligomers of the parent CHA zeolite form and arrange around micelles that exhibit cubic symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a BEA zeolite having an atomic level tetragonal symmetry arranged at a mesoscale with a cubic symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent BEA zeolite, oligomers of the parent BEA zeolite form and arrange around micelles that exhibit cubic symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a MWW zeolite having an atomic level hexagonal symmetry arranged at a mesoscale with cubic symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MWW zeolite, oligomers of the parent MWW zeolite form and arrange around micelles that exhibit cubic symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a FAU zeolite having an atomic level cubic symmetry arranged at a mesoscale with cubic symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent FAU zeolite, oligomers of the parent FAU zeolite form and arrange around micelles that exhibit cubic symmetry at the mesoscale.

[0088] In embodiments herein, the product produced by the above method and demonstrated in the examples herein is characterized by a mesophase having hexagonal symmetry. In some embodiments, the product is a 2D-hexagonal ordered mesoporous zeolite. HOCMM with a mesophase having hexagonal symmetry is characterized by a hexagonal mesoporous channel direction, wherein the CMM microporous channels are in the walls of the mesoporous structure. The hexagonal mesophase may have one of p6m, p6mm or p63 / mmc symmetries. In embodiments herein, the hexagonal mesophase has p6mm symmetry, and secondary XRD peaks associated with the periodic arrangement of mesopores are present at one or more of the (11) and (20) reflections. In embodiments herein, the hexagonal mesophase has p6mm symmetry, and secondary XRD peaks are present at both the (11) and (20) reflections. In embodiments herein, the hexagonal crystalline mesophase possesses p6mm symmetry, and a high degree of long-range hexagonal p6mm mesophase order is observable microscopically through electron beam observation perpendicular to pores along the

[110] zone axis and / or parallel to pores along the

[001] zone axis. In these embodiments, the CMM structure is arranged with hexagonal p6mm symmetry at the mesoscale, wherein the CMM particles (regardless of their atomic level symmetry or structure) are arranged around micelles (at the mesoscale), and thereby the micelles are arranged to exhibit hexagonal symmetry. Thus, HOCMMs having a hexagonal p6mm mesophase include CMMs characterized by atomic level symmetry and possessing micropores inherent to this type of CMM, which are arranged with hexagonal p6mm symmetry at the mesoscale level with mesopores, wherein the walls of the mesopores and the bulk of the mesostructure between the mesopores are characterized by the CMM (e.g., crystalline zeolite). This is produced as described herein by forming oligomers of the intrinsic CMM and arranging those oligomers around micelles that exhibit hexagonal symmetry on the mesoscale. In one embodiment, a HOCMM is provided that includes an MFI zeolite having an atomic level orthorhombic symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MFI zeolite, oligomers of the parent MFI zeolite form and arrange around micelles that exhibit hexagonal symmetry on the mesoscale. In one embodiment, a HOCMM is provided that includes a CHA zeolite having an atomic level trigonal symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent CHA zeolite, oligomers of the parent CHA zeolite form and arrange around micelles that exhibit hexagonal symmetry on the mesoscale. In one embodiment, a HOCMM is provided that includes a BEA zeolite having atomic level tetragonal symmetry arranged at a mesoscale with a hexagonal p6mm symmetry, wherein during the synthesis of hierarchically ordered zeolites from a parent BEA zeolite, oligomers of the parent BEA zeolite are formed and arranged around micelles exhibiting hexagonal symmetry at the mesoscale.In one embodiment, a HOCMM is provided that includes a MWW zeolite having an atomic level hexagonal symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MWW zeolite, oligomers of the parent MWW zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a FAU zeolite having an atomic level cubic symmetry arranged at a mesoscale of hexagonal p6mm symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent FAU zeolite, oligomers of the parent FAU zeolite form and arrange around micelles that exhibit hexagonal symmetry at the mesoscale.

[0089] In embodiments herein, the product produced by the above method and demonstrated in the examples herein is characterized by a high degree of long-range lamellar mesophase order. In some embodiments, the product is a mesoporous zeolite with a lamellar mesophase order. The HOCMM of the mesophase with lamellar symmetry is characterized by a lamellar mesoporous channel direction, wherein the CMM microporous channels are in the walls of the mesostructure. In these embodiments, the CMM structure is arranged with lamellar symmetry on the mesoscale, wherein the CMM particles (regardless of their atomic level symmetry or structure) are arranged around the micelles (on the mesoscale), and thereby the micelles are arranged to exhibit lamellar symmetry. In some embodiments, the lamellar symmetry is p2, p1 or pm symmetry. In some embodiments, the lamellar symmetry is p2 symmetry, wherein the secondary XRD peak associated with the periodic arrangement of the mesopores is present at least at the (200) reflection. In some embodiments, the high degree of long-range lamellar mesophase order can be observed by microscopy, by electron beam observation in a direction parallel or perpendicular to the

[100] crystal band axis. Thus, HOCMMs with lamellar mesophases include CMMs characterized by atomic level symmetry and possessing micropores intrinsic to this type of CMM, which are arranged with lamellar symmetry at the mesoscale level with mesopores, wherein the walls of the mesopores and the bulk of the mesostructure between the mesopores are characterized by the CMMs. This is produced as described herein by forming oligomers of the intrinsic CMMs and arranging those oligomers around micelles exhibiting lamellar symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes an MFI zeolite having atomic level orthorhombic symmetry arranged at the mesoscale with lamellar symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MFI zeolite, oligomers of the parent MFI zeolite are formed and arranged around micelles exhibiting lamellar symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a CHA zeolite having an atomic level trigonal symmetry arranged at a mesoscale with lamellar symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent CHA zeolite, oligomers of the parent CHA zeolite form and arrange around micelles that exhibit lamellar symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes a BEA zeolite having an atomic level tetragonal symmetry arranged at a mesoscale with lamellar symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent BEA zeolite, oligomers of the parent BEA zeolite form and arrange around micelles that exhibit lamellar symmetry at the mesoscale. In one embodiment, a HOCMM is provided that includes an MWW zeolite having an atomic level hexagonal symmetry arranged at a mesoscale with lamellar symmetry, wherein during the synthesis of a hierarchically ordered zeolite from a parent MWW zeolite, oligomers of the parent MWW zeolite form and arrange around micelles that exhibit lamellar symmetry at the mesoscale.In one embodiment, a HOCMM is provided that includes a FAU zeolite having atomic level cubic symmetry arranged in a lamellar symmetry mesoscale, wherein during the synthesis of hierarchically ordered zeolites from a parent FAU zeolite, oligomers of the parent FAU zeolite are formed and arranged around micelles exhibiting lamellar symmetry in the mesoscale.

[0090] In embodiments where the CMM structures are arranged with lamellar symmetry at the mesoscale, the lamellar symmetry is primarily observed in the as-prepared material (i.e., before calcination). In the absence of CMM interconnections between lamellar structures, there is a tendency to collapse during calcination. In some embodiments, CMMs, such as zeolite crystal structures, arranged with lamellar symmetry as provided herein can be peeled off to form sheets of CMMs, such as zeolite nanosheets. In some embodiments, CMMs such as zeolite crystal structures arranged with the lamellar symmetry provided herein can retain the lamellar symmetry by using pillaring techniques known in the art, for example, where a silica source such as tetraethyl orthosilicate (TEOS) is condensed in the lamellar structure and crystallized during calcination to retain the lamellar structure and prevent collapse (see, for example, Na, K. et al. "Pillared MFI Zeolite Nanosheets of a Single-unit-cell Thickness." J. Am. Chem. Soc. 132, 4169-4177. In embodiments where the HOCMMs formed herein possess mesoscale lamellar symmetry with a pillared lamellar structure, they can be used, for example, as catalytic materials or catalytic support materials.

[0091] The HOCMM produced according to the present disclosure is effective as a catalyst or a component of a catalyst in the hydrocracking of hydrocarbon oils. HOCMM can be used as a carrier on which one or more active metal components are loaded as a hydrocracking catalyst. The active metal component is loaded, for example, loaded on a surface including a mesopore wall surface, a micropore wall surface, or a mesopore and a micropore wall surface; the active metal component is loaded according to a known method, for example, an aqueous solution of the active metal component is provided and HOCMM is subjected to impregnation, initial wetness impregnation and evaporation as a catalyst support material, or any other suitable method. In some embodiments, the CMM of HOCMM includes zeolite. In some embodiments, the CMM of HOCMM includes one or more zeolite types AEI, *BEA, CHA, FAU, MFI, MOR, LTL, LTA or MWW. In some embodiments, the CMM of HOCMM includes FAU zeolite.

[0092] The content of HOCMM and active metal components is appropriately determined according to the object. In some embodiments, the hydrocracking catalyst includes HOCMM as a carrier, and an inorganic oxide component, typically as a binder and / or a granulating agent. For example, the carrier particles (before loading one or more hydrocracking active metal components) may contain HOCMM in the following range: about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50 or 20-40 weight %, wherein the remaining content is an inorganic oxide. In some embodiments, the support particles (before loading one or more hydrocracking active metal components) may contain HOCMM in the following ranges: about 0.1-99, 0.1-90, 0.1-80, 0.1-70, 0.1-50, 0.1-40, 2-99, 2-90, 2-80, 2-70, 2-50, 2-40, 20-100, 20-90, 20-80, 20-70, 20-50 or 20-40 weight percent, with the remainder being inorganic oxides and one or more other zeolite materials.

[0093] As the inorganic oxide component, any material used in hydrocracking or other catalyst compositions in the related art can be used. Examples thereof include alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, silica-alumina-zirconia, alumina-zirconia-titania, phosphorus-alumina-zirconia, alumina-zirconia-titania, and phosphorus-alumina-titania.

[0094] The active metal component may include one or more metals or metal compounds (oxides or sulfides) known in the hydrocracking field, including those selected from the 6th, 7th, 8th, 9th and 10th families of the periodic table IUPAC. In some embodiments, the active metal component is one or more of Mo, W, Co or Ni (oxides or sulfides). Other active metal components can be contained in the catalyst at an effective concentration. For example, the total active component content in the hydrocracking catalyst can exist in an amount known in the relevant art, such as about 0.01-40, 0.1-40, 1-40, 2-40, 5-40, 0.01-30, 0.1-30, 1-30, 2-30, 5-30, 0.01-20, 0.1-20, 1-20, 2-20 or 5-20W % in terms of metal, oxide or sulfide. In some embodiments, the active metal component is loaded using an oxide solution, and before use, the hydrocracking catalyst is sulfided.

[0095] Example

[0096] The HOCMM produced in the examples herein exhibit a significant degree of well-defined long-range mesoporous order, as given by the low-angle XRD pattern. The structural and textural properties of some samples are provided in Table 3. The parent zeolite used in the examples and comparative examples has a FAU framework, zeolite Y (obtained from Zeolyst International, product name CBV 720), and is referred to herein as zeolite HY-15, with a SAR of about 30 (Si / Al atomic ratio of 15). Although the examples are shown with respect to this particular zeolite, the methods herein can be applied to another type of parent CMM from another source and as described herein, whether obtained from a commercial manufacturer or from a separate synthesis process. Therefore, the resulting material composition has a mesoporous structure with micropores and a CMM structure corresponding to the parent CMM. The solution was prepared at room temperature (RT) and under stirring at 500RPM.

[0097] Characterization in this article is carried out as follows. Powder x-ray diffraction patterns were obtained as follows: using a Bruker D8twin diffractometer, operated at 40kV and 40mA, with Cu Kα radiation (λ=0.154nm) and a step size of 0.02. N2 physical adsorption measurements were performed using a Micromeritics ASAP 2420 instrument at 77K. All samples were degassed at 350°C for 12h before analysis. Specific surface area and pore size distribution were calculated using Brunauer-Emmett-Teller (BET) and non-local density functional theory (NLDFT) models. The t-plot method was used to calculate the micropore volume. High-resolution transmission electron microscopy (TEM) studies were performed using a FEI-Titan ST electron microscope operated at 300kV. Scanning electron microscopy (SEM) images were obtained using a Nova Nano HR-SEM 240 microscope operated at 4kV. The samples were sputter-coated with platinum (Pt) before analysis to eliminate charge effects. The Si / Al ratio was calculated as follows: by solid-state magic angle spinning nuclear magnetic resonance (MAS-NMR) experiments using a Bruker Advance 400 MHz instrument, applying 4 μs radio frequency pulses and a 60 second cycle delay. In contrast, the bulk Si / Al ratio of the zeolite was calculated by inductively coupled plasma-emission spectroscopy (ICP-OES) analysis using a 5100 ICP-OES Agilent instrument. Prior to analysis, the sample was mixed with hydrofluoric acid (HF) and nitric acid (HNO3) and digested at 260°C and 160 bar using an UltraWAVE microwave digestion system (Milestone).

[0098] To obtain electron micrographs for tomography reconstruction, zeolite powder was deposited on Quantifoil 300 mesh TEM grids supporting a 2 nm thick continuous carbon film on a holey carbon membrane. Prior to zeolite deposition, a dilute solution of gold nanoparticles (AuNPs) with a diameter of approximately 5 nm was dispersed on the TEM grid. The AuNPs will be used in the alignment of the tomography tilt series. To protect the specimen from beam-induced damage during the long exposure times required for tomography data acquisition, tomography tilt series were acquired on a Krios G4 (ThemoFisher TM) electron microscope at liquid nitrogen temperature. The true temperature of the stage level is about -183 ° C. The tilt series is acquired in energy filtering (EF) mode, using a 30eV slit to increase the contrast of bright field TEM images. Detection is performed on a Falcon i electron direct detector camera, which runs in electron counting mode with a frame size of 4096 pixels. To keep the total exposure dose low, only sample tracking is performed after each tilt series during data acquisition. Refocusing is performed manually about every 10 images. The angular range is ± 64 °, with a tilt step of 1 °. The tilt series are aligned in the IMOD software using 13 AuNPs as reference markers, which are clearly visible at each tilt angle. Before reconstruction, 2 image binnings are performed to increase SNR and reduce calculation time. To enhance the visibility of holes in 3D tomograms, images are filtered using an average background subtraction filter (ABSF) implemented as a script in Digital Micrograph. The SIRT reconstruction algorithm runs 100 iterations and uses a relaxation factor of 1.

[0099] Example 1A: 2.4 grams of NH4OH were added to 28.3 grams of water while stirring. To the solution was dispersed an amount of 1.0 grams of dry zeolite HY-15 and further stirred for 0.25 hours. Then, 0.4 grams of CTAB was added and further stirred for 0.5 hours. The resulting solution was further stirred for 1 hour and then hydrothermally treated at 130°C for 24 hours. The resulting solid was filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain AH-CT (wherein AH refers to ammonium hydroxide and CT refers to CTAB). The AH-CT synthesized according to this procedure exhibits disordered mesopores and Figures 3A-4B The SEM images are shown in Figure 6 and the structural and textural properties are provided in Table 3.

[0100] In an alternative procedure, an amount of 2.0 grams of dry zeolite HY-15 was dispersed in 56.6 grams of water while stirring. 0.77 grams of hexadecyltrimethylammonium bromide (CTAB) was added to the solution and further stirred for 0.5 hours. Subsequently, 4.75 grams of an aqueous solution of ammonium hydroxide (30 wt %) was added dropwise to the mixture under stirring. The resulting solution was further stirred for 0.5 hours and then hydrothermally treated at 130°C for 24 hours. The resulting solid was filtered, washed with water and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain AH-CT, which exhibited disordered mesopores.

[0101] Example 1B: A procedure for the synthesis of a 2D-hexagonal ordered mesoporous FAU-type zeolite is provided. NH4OH in an amount of 2.4 grams is added to 28.3 grams of water while stirring. A dried zeolite HY-15 in an amount of 1.0 grams is dispersed in the alkaline solution and further stirred for 0.25 hours. Then, dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium chloride (DOAC) in an amount of 1.5 milliliters (42.0 weight % in methanol) is added and further stirred for 0.5 hours. The resulting solution is further stirred for 1 hour and then hydrothermally treated at 130°C for 24 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain AH-TMS (wherein TMS refers to DOAC, dimethyloctadecyl (3-trimethoxysilyl-propyl)-ammonium chloride). The AH-TMS formed according to this procedure exhibits 2D-hexagonal ordered mesoporous symmetry and Figures 3A-4B The SEM images are shown in Figure 6 and the structural and textural properties are provided in Table 3.

[0102] In an alternative procedure, 2.0 grams of dried zeolite HY-15 is dispersed in 56.6 grams of water while stirring. To the dispersion is added 3.0 milliliters of organosilane DOAC (42.0 wt. % in methanol) and further stirred for 0.5 hours. Subsequently, 4.75 grams of an aqueous ammonium hydroxide solution (30 wt. %) is added dropwise to the mixture under stirring. The resulting solution is further stirred for 0.5 hours and then hydrothermally treated at 130°C for 24 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain AH-TMS. The AH-TMS formed according to this procedure has 2D-hexagonal ordered mesoporous symmetry (as in Figures 5A-5C (this is clearly seen in the TEM image of the AH-TMS presented in FIG. ).

[0103] Example 1C: An amount of 0.6 g of urea was added to 28.3 g of water to form a homogeneous solution. Into the solution was dispersed an amount of 1.0 g of dry zeolite HY-15, and further stirred for 0.5 hours. Subsequently, 20 ml of water and 1.5 ml of DOAC (42.0 wt. % in methanol) were added, and further stirred for 2 hours. The resulting solution was subjected to hydrothermal treatment at 130°C for 5 days. The resulting solid was filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain U-TMS (wherein U refers to urea). The U-TMS formed according to this procedure exhibits poorly defined mesopores and Figures 3A-4B The SEM images are shown in Figure 6 , and the structural and textural properties are provided in Table 3.

[0104] In an alternative procedure, 1.2 grams of urea was dissolved in 60.0 grams of water to form a homogeneous solution. 2.0 grams of dry zeolite HY-15 was added to the mixture and stirred for 10 minutes. Subsequently, 3.0 milliliters of DOAC (42.0 weight percent in methanol) was added. The resulting solution was stirred for 0.5 hours and then hydrothermally treated at 130°C for 72 hours. The resulting mixture was filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain U-TMS, which does not have a defined mesopore.

[0105] The calcined products from Examples 1A-1C and the reference HY-15 zeolite were Figures 3A-4B Characterization, where: Figure 3A The low angle XRD pattern is depicted, and Figure 3B High-angle XRD patterns are depicted, where the intensity is expressed in arbitrary units (au) and plotted against frequency 2θ (°); Figure 4A The N2 physical adsorption isotherm was plotted, and the adsorbed N2 (cm 3 ·g -1 ) relative to the relative pressure (P / P0); and Figure 4B The nonlocalized density functional theory (NLDFT) pore size distribution is plotted, and dV / dlogW (cm 3 ·g -1)(wherein "a" corresponds to commercial USY (zeolite HY-15), "b" corresponds to AH-CT, "c" corresponds to AH-TMS, and "d" corresponds to U-TMS). In Example 1B, the product hierarchically ordered zeolite is a 2D-hexagonally ordered mesoporous FAU-type zeolite having mesoporous channels arranged in a hexagonal manner as observed in the

[100] and

[110] directions, wherein the FAU microporous channels are in the walls and in a large number of mesostructures between the mesopores.

[0106] Figure 5A -C is a TEM micrograph of calcined AH-TMS (formed according to the alternative procedure in Example 1B) showing hexagonal mesoporous channels in the

[100] and

[110] directions, where: Figure 5A TEM micrograph showing at 50 nanometer scale; Figure 5B TEM micrographs showing the

[100] direction and the

[110] direction at a scale of 20 nanometers, and the corresponding schematic diagram and unit cell dimensions are also depicted; and Figure 5C TEM micrograph shown in the

[100] direction at the 10 nm scale (with an overlay schematic of the intrinsic zeolite structure).

[0107] Figure 6 The following images are shown: (A) parent zeolite HY-15; and the calcined products herein, (B) AH-CT, (C) AH-TMS, and (D) U-TMS. The image of AH-CT (B) does not indicate a significant change in morphology even at the crystal edges, while the image of AH-TMS does indicate a change in morphology that indicates that the functionality of the organosilane, with a more bulky head and silanol groups than CTAB, leads to improved dissolution and reassembly. With respect to U-TMS, the urea-mediated synthesis significantly improves crystallinity ( Figure 6 ), but the mesoporous structure is poorly defined, e.g. Figure 3A Figure (d) is clear. Although it is not desired to be bound by theory, these comparative results show that the dissolution rate not only affects recrystallization, but also affects supramolecular self-assembly. The mesophase organization can be affected by many physicochemical phenomena, including Coulomb interaction, hydration energy and hydrophobic effect between organic and inorganic species. In the absence of strong base cations, the surfactant-zeolite interaction plays a key role in promoting synergistic self-assembly to induce mesophase. In the case of AH-TMS, zeolite dissolution is instantaneous, and importantly, -Si(OCH3)3 groups on the organosilane head group can be easily hydrolyzed to interact with the anionic zeolite component to promote mesophase. On the contrary, in the case of U-TMS, the concentration of the anionic inorganic component gradually changes over time, so the charge balance at the micelle interface is gradually changed, destroying the mesophase formation.

[0108] A high degree of long-range order Figure 3A The low angle XRD pattern "c" of Example 1A is clear, which exhibits Bragg reflections at angles corresponding to the 100, 110 and 200 planes, indicating hexagonal mesopore symmetry in AH-TMS. In contrast, in Example 1A, the use of relatively small template or surfactant molecules (CTAB) leads to diffusion within the zeolite pores, causing uneven dissolution and preventing comprehensive recombination. This is clear from the low angle XRD patterns "b" and "d", which have uniform pore size distribution (PSD) ( Figure 4A ), but did not show a high degree of long-range order, which is attributed to the inhomogeneous zeolite dissolution and restricted supramolecular self-assembly. For all samples, the retention of the underlying zeolite structure is Figure 3B The high-angle XRD patterns of the AH-TMS are clear, which is consistent with those of the parent zeolite FAU zeolite. In addition, AH-TMS shows excellent hierarchically ordered mesopores, as indicated by the characteristic type IV isotherms with H1 hysteresis ( Figure 4A In addition, the high mesopore volume and narrow pore size distribution further support the existence of long-range ordered mesopores ( Figure 4B ).

[0109] Example 2A: A procedure for the synthesis of a 3D cubic ordered mesoporous FAU-type zeolite is provided. A 0.6 gram amount of urea is added to 10.0 grams of water to form a homogeneous solution. To the solution is added 1.0 gram of dry zeolite HY-15 and stirred for 0.5 hours. Subsequently, 20 milliliters of water, 0.1 grams of ammonium nitrate (NH4NO3) as an ionic co-solute source, and 1.5 milliliters of DOAC (42.0 wt % in methanol) are gradually added, and the mixture is further stirred for 2 hours. The resulting solution is subjected to a hydrothermal treatment at 130°C for 5 days. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain UN-TMS-130 (wherein N refers to nitrate, and "130" refers to the hydrothermal treatment temperature). The UN-TMS-130 formed according to this procedure exhibits 3D-cubic ordered mesoporous symmetry, and at Figures 7A-8B The TEM images are shown in Figures 9A-9C , and the structural and textural properties are provided in Table 3.

[0110] In an alternative procedure, 1.2 grams of urea was dissolved in 60.0 grams of water to form a homogeneous solution. To the mixture was added 0.2 grams of ammonium nitrate (NH4NO3) as an ionic co-solute source and stirred to form a homogeneous solution. 2.0 grams of zeolite HY-15 was added and stirred for 10 minutes. Subsequently, 3.0 milliliters of DOAC (42.0 wt. % in methanol) was added. The resulting solution was stirred for 0.5 hours and then hydrothermally treated at 130°C for 72 hours. The resulting solid was filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product was calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain UN-TMS. The calcined UN-TMS formed according to this procedure exhibits 3D cubic ordered mesoporous symmetry, as shown in Figures 10A-10B This is clearly shown in the TEM images presented in Figure 2.

[0111] Example 2B: A similar procedure as in the first procedure of Example 2A herein was followed, except that 1.0 g of urea and 2.0 ml of DOAC (42.0 wt. % in methanol) were used, and the hydrothermal treatment was performed at 150°C for 72 hours. The calcined product was UN-TMS-150, which possessed 3D cubic ordered mesoporous symmetry. UN-TMS-150 from this procedure was Figures 7A-8B and its TEM image is presented in Figures 12A-12C , and the structural and textural properties are provided in Table 3.

[0112] The calcined medium pore zeolite products from Examples 2A and 2B and the reference HY-15 zeolite were Figures 7A-8B Characterization, where: Fig. 7A The low angle XRD pattern is depicted, and Figure 7B Depicted are high-angle XRD patterns, where intensity in arbitrary units (au) is plotted versus frequency 2θ (°); Fig. 8A Plotting the adsorbed N2(cm 3 ·g -1 ) N2 physical adsorption isotherm with respect to relative pressure (P / P0); and Figure 8B Plot dV / dlogW(cm 3 ·g -1 ) (where "a" corresponds to commercial USY (zeolite HY-15), "b" corresponds to UN-TMS-130, and "c" corresponds to UN-TMS-150). In Examples 2A and 2B, the product hierarchically ordered zeolite is a 3D-cubic ordered mesoporous FAU-type zeolite having cubic mesoporous channels existing in the

[100] and

[110] directions, wherein the FAU microporous channels are in the walls and in a large number of mesostructures between the mesopores.

[0113] Fig.9A -C presents a TEM micrograph of calcined UN-TMS-130 formed according to the first procedure of Example 2A, showing cubic mesoporous channels in the

[111] and

[110] directions, wherein Fig.9A is the image in the

[111] direction on a 100 nm scale, and Fig. 9B and 9C is the image in the

[112] direction at 50 nm scale (where Fig. 9B The image relative to Fig. 9C (enlarged image). Fig. 10A -B is a TEM micrograph of calcined UN-TMS formed according to the second procedure of Example 2A, showing cubic mesoporous channels in the

[111] and

[110] directions, wherein: Fig. 10A TEM micrographs at the 100-nm scale are shown; Fig. 10B TEM micrographs are shown on a 20 nm scale in the

[110] direction and in the

[111] direction; and Fig. 10C A schematic diagram of the FAU unit cell and its dimensions and arrangement are depicted to provide long-range mesoporous order. The high degree of long-range order is derived from Fig. 7A The low angle XRD pattern of the zeolite is clear, showing Bragg reflections 211, 220, 321, 400, 420 and 332, which are characteristic of the pore symmetry of the bicontinuous gyroid (cubic) (Ia-3d) (where the reflections at 321, 400, 420 and 332 are magnified). The retention of the zeolite structure below is from Figure 7B The high-angle XRD patterns of UN-TMS-130 and UN-TMS-150 are clear, which are consistent with those of the parent zeolite FAU zeolite. In addition, UN-TMS-130 and UN-TMS-150 demonstrate excellent hierarchical ordered mesopores, as shown in Fig. 8A The N2 physical adsorption isotherm is depicted as a characteristic type IV isotherm with H1 hysteresis. Figure 8B The high mesopore volume and narrow pore size distribution demonstrated in the samples further support the existence of long-range ordered mesopores. Fig.11 Electron tomography reconstructions of UN-TMS-150 are presented, with insets to magnify the pore architecture and show overlays of the structure. Fig. 12A -C presents the TEM micrographs and corresponding structural diagrams of UN-TMS-150, where Fig. 12A is an image showing a TEM micrograph at the

[100] orientation on a 20 nm scale, Fig. 12B is the image at the

[110] orientation on the 50 nm scale, and Fig. 12C is an image of the

[111] orientation at the 10 nm scale. Fig. 12A and12B The inset shows an enlarged image and Fig. 12C The inset in the figure shows the selected area electron diffraction (SAED). UN-TMS-150 synthesized at higher temperature exhibits improved textural properties due to the thorough removal of extra-framework aluminum. The 3D mesostructure by electron tomography (ET) reveals the uniform distribution of mesoporous channels within the zeolite volume. A longitudinal slice cut through the middle of the zeolite crystallite shows a continuous network of mesopores developing along a single crystallographic direction. Fig.11 The inset in Figure 2 highlights the 3D spatial uniformity of the hierarchical pore architecture. The interconnected mesoporous network formed by the zeolite framework extends from the outer face of the zeolite crystal to its core.

[0114] In addition, when comparing the product of Example 1C (U-TMS) with the product of Examples 2A and 2B (UN-TMS), the benefit of the ionic cosolute contribution of nitrate is clear. The ionic cosolute is used to influence the cubic micelle shape through the Hofmann effect, and the FAU-type zeolite oligomers are arranged around it. In Example 1C, there is a certain degree of periodicity in the arrangement of mesopores, which may come from a bimodal system or structural collapse, however, compared with the products of Examples 2A and 2B with nitrate anions, there is a significant lack of any long-range order, which is observed by low-angle XRD, showing reflection characteristics of a gyratory bicontinuous (cubic) mesoporous structure (Ia-3d).

[0115] Example 3A: A procedure for the synthesis of 2D hexagonal ordered mesoporous FAU-type zeolite using sulfate as an ionic co-solute is provided. Urea in an amount of 0.6 grams is added to 10.0 grams of water to form a homogeneous solution. To the solution is added an amount of 1.0 grams of dry zeolite HY-15 and stirred for 0.5 hours. Subsequently, 20 milliliters of water, 0.165 grams of ammonium sulfate ((NH4)2SO4) and 1.5 milliliters of DOAC (42.0 wt % in methanol) are gradually added, and the mixture is further stirred for 2 hours. The resulting solution is subjected to a hydrothermal treatment at 130°C for 72 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain US-TMS (wherein U refers to urea, S refers to sulfate, and TMS refers to DOAC). The US-TMS formed according to this procedure exhibits 2D hexagonal ordered mesoporous symmetry, and at Figures 13A-14B The TEM images are shown in Figures 15A-15E , and the structural and textural properties are provided in Table 3.

[0116] In an alternative procedure, urea in an amount of 1.2 grams is dissolved in 60.0 grams of water to form a homogeneous solution. To the mixture is added 0.33 grams of ammonium sulfate (NH4)2SO4) as an ionic cosolute source and stirred until homogeneous. Thereafter, 2.0 grams of dry zeolite HY-15 is added and stirred for 10 minutes. Subsequently, 3.0 milliliters of DOAC (42.0 wt % in methanol) is added. The resulting solution is stirred for 0.5 hours and then hydrothermally treated at 130°C for 72 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain US-TMS, which has 2D hexagonal ordered mesoporous symmetry.

[0117] Example 3B: A procedure for the synthesis of 2D layered ordered mesoporous FAU-type zeolites using perchlorate as an ionic cosolute is provided. Urea in an amount of 0.6 grams is added to 10.0 grams of water to form a homogeneous solution. 1.0 grams of dry zeolite HY-15 is added to the solution and stirred for 0.5 hours. Subsequently, 20 milliliters of water, 0.46 grams of sodium perchlorate (NaClO4), and 1.5 milliliters of DOAC (60.0 weight percent in methanol) are gradually added, and the mixture is further stirred for 2 hours. The resulting solution is subjected to hydrothermal treatment at 130°C for 72 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6.0 hours at a heating rate of 60°C / hour to obtain UC-TMS (wherein U refers to urea, C refers to perchlorate, and TMS refers to DOAC). The as-prepared UC-TMS formed according to the procedure exhibits 2D layered ordered mesoporous symmetry. As-prepared and calcined UC-TMS Fig.13A The calcined UC-TMS was characterized in Fig. 13B , 14A -14B, and the structural and textural properties are provided in Table 3.

[0118] The effect of anion selection is clear when comparing Examples 3A and 3B. The choice of perchlorate ion co-solute affects the shape of the lamellar micelles, while the choice of nitrate ion co-solute affects the shape of the cubic micelles through the Hofmann effect. In both examples, the FAU-type zeolite oligomers are arranged around the shaped micelles.

[0119] The as-prepared and calcined products from Examples 3A-3B were Fig.13A and the calcined products from Examples 3A-3B were characterized in Fig. 13B and 13A -13B (where "a" corresponds to US-TMS and "b" corresponds to UC-TMS). Fig.13AThe low angle XRD pattern is depicted, and Fig. 13B High angle XRD patterns are depicted, where intensity in arbitrary units (au) is plotted versus frequency 2θ (°), with the as-prepared pattern shown as a dashed line and the calcined pattern shown as a solid line. Fig.14A Plotted adsorbed N2 (cm 3 ·g -1 ) with respect to the N2 physical adsorption isotherm of the relative pressure (P / P0), and Fig. 14B Depicted is the plot of dV / dlogW(cm 3 ·g -1 The highly long-range order of as-prepared and calcined US-TMS is shown in Figure 2. Fig.13A The low-angle XRD pattern shows Bragg reflection peaks at 100, 110 and 200, indicating 2D hexagonal ordered mesoporous symmetry. Fig.13A It is also clear that the Bragg reflection peaks 100 and 200 indicate 2D layered (p2) mesopore symmetry, but this order is lost as the structure collapses during calcination. The retention of the intrinsic zeolite structure is due to Fig. 13B It is clear in the figure that the high angle XRD patterns are consistent with those of the parent zeolite FAU zeolite.

[0120] Fig.15A -E presents a TEM micrograph of US-TMS synthesized in the first procedure of Example 3A, wherein Fig.15A is an image at the 20-nanometer scale with a corresponding structural diagram; Fig.15A for Fig.15A A magnified view of a portion of the image in FIG, with a fast Fourier transform plot inset; Fig. 15C The image is at 50 nm scale, showing the selected area electron diffraction (SAED) in the inset; Fig.15D is an image at a 50 nanometer scale; and Fig.15E An image at the 20-nanometer scale with a corresponding structural diagram.

[0121] Example 4A: A procedure for the synthesis of a 2D layered ordered mesoporous FAU-type zeolite is provided. An amount of 1.2 grams of urea is dissolved in 60.0 grams of water to form a homogeneous solution. To the mixture is added 2.0 grams of zeolite HY-15 and stirred. 0.92 grams of sodium perchlorate (NaClO4) is added and stirred for 10 minutes. Subsequently, 3.0 milliliters of DOAC (42.0 wt % in methanol) is added. The resulting solution is stirred for 0.5 hours and then hydrothermally treated at 130°C for 72 hours. The resulting solid is filtered, washed with water, and dried at 120°C for 24 hours. The synthesized product is calcined at 550°C in air for 6 hours at a heating rate of 60°C / hour to obtain UC-TMS (wherein Y refers to zeolite Y, C refers to perchlorate, U refers to urea, and TMS refers to DOAC). The as-prepared UC-TMS formed according to this procedure exhibits 2D layered ordered mesoporous symmetry and Fig.16A -B characterization, where TEM images are presented in Figures 17A-17C middle.

[0122] Example 4B: Procedure The procedure of Example 4A was followed with the following exceptions: 4.75 g of NH4OH was used as alkaline reagent instead of urea.

[0123] In Example 4A, the product hierarchically ordered zeolite is a 2D lamellar ordered mesoporous FAU-type zeolite having lamellar mesoporous channels existing in the

[100] direction, wherein the FAU microporous channels are in the walls and in a large number of mesostructures between the mesopores. Fig.16A describes the low angle XRD pattern, and Fig. 16B High angle XRD patterns are depicted, where "a" corresponds to commercially available USY (zeolite HY-15) and "b" corresponds to UC-TMS; Fig.17A -C describes the UC-TMS layered structure, where: Fig.17A TEM micrographs at the 50 nm scale in a plane oriented

[100] are shown; Fig. 17B TEM micrographs at the 20 nm scale are shown; and Fig. 17C TEM micrographs of the

[110] plane orientation at the 50 nm scale are shown. The high degree of long-range order is derived from Fig.16A The low-angle XRD pattern shows Bragg reflection peaks at 100 and 200, indicating 2D layered (p2) mesopore symmetry. The retention of the intrinsic zeolite structure is Fig. 16B It is clear in the figure that the high angle XRD patterns are consistent with those of the parent zeolite FAU zeolite.

[0124] According to the embodiments herein, hierarchically ordered FAU-type frameworks exhibiting 2D hexagonal (p6mm), 3D cubic (Ia-3d), and 2D lamellar (p2) mesoporous symmetries are prepared for the first time by methodical post-synthesis recombination.

[0125] Example 5 - Acidity Characterization: Acid site characterization was performed by Fourier transform infrared spectroscopy (FTIR) using a Nicolet 6700 spectrophotometer with pyridine as the probe molecule. Prior to analysis, pelletized samples were heated at 450°C under vacuum (10 -5 mbar) for 24 h. After cooling to room temperature, pyridine vapor was metered periodically for 0.5 h. Subsequently, the physically adsorbed pyridine was removed under vacuum at 150 °C for 2 h before recording the FTIR spectrum. Acid sites were quantified using the following formula

[0126] C BAS =IMEC BAS -1 ×IA BAS ×πR 2 / W

[0127] C LAS =IMEC LAS -1 ×IA LAS ×πR 2 / W

[0128] Where C is the concentration of acid sites (BAS-Brönsted acid sites and LAS-Lewis acid sites) (μmol / g zeolite), IMEC BAS and IMEC LAS Refers to the integrated molar extinction coefficient (BAS-1.67cm / μmol; LAS-2.22cm / μmol), IA BAS and IA LAS Integrated absorbance (cm -1 ), R (cm) and W (mg) are the radius and weight of the zeolite particle / disk.

[0129] Fig.18 Depicted are the FTIR spectra of the parent zeolite (a), and the HOCMM herein comprising UN-TMS-150 (b) and US-TMS synthesized in the first procedure of Example 3A (c). The Brønsted acid site is at wave number 1545 cm -1 The Lewis acid site is indicated at wave number 1445 cm -1Indicated at. Table 4 shows the following acid properties: parent zeolite, UN-TMS-150, and US-TMS synthesized in the first procedure of Example 3A. Compared with the parent zeolite, the total acidity of the synthesized HOCMM is lower, which is attributed to the removal of non-framework Al in the parent zeolite during the recombination; the framework Al exists as a Bronsted acid site (0.28mmol / g). The acid sites are reorganized and distributed in the HOCMM as both new Lewis acid sites (~0.1mmol / g) and Bronsted acid sites (~0.25mmol / g). Despite having a lower concentration of zeolite acid sites compared to the parent zeolite, the synthesized HOCMM is effective as a catalyst support. Compared with the parent zeolite, the Bronsted / Lewis acid site ratio of the synthesized HOCMM is higher.

[0130] Example 6 - Additional Characterization: Additional Properties of the Parent Zeolite (a) and the HOCMM Comprising UN-TMS-150 (b) and US-TMS Synthesized in the First Procedure of Example 3A (c) 29 Si MAS-NMR and 7 AlMAS-NMR spectroscopy showed Fig.19A -B. 29 Si-NMR spectroscopy ( Fig.19A ) shows two main resonances at ~106 ppm and ~101 ppm, corresponding to silicon atoms in 4Si(0Al) and 3Si(1Al) environments, namely Q 4 and Q 3′ Silicon dioxide. 9 The Si / Al ratio calculated from Si-NMR spectroscopy (14.8) and inductively coupled plasma analysis (Si / Al ~ 8.9) revealed that the parent zeolite has nearly 40% of its aluminum as non-framework species in octahedral coordination, which can be seen as 27 The sharp resonance at '~0ppm' in the Al-NMR spectrum (AlO) Fig.19B ). The presence of high non-framework Al can be detrimental in catalytic reactions because it causes micropore blockage and changes in product selectivity and coke composition. In contrast, the HOCMM characterized in this paper has a tetrahedral coordination (Al T ) show a higher concentration of framework Al atoms, as seen by the broad resonance at '~60 ppm'. In particular, the UN-TMS-130 pattern (b) shows 'Al' atoms predominantly in Td coordination. Without wishing to be bound by theory, this is expected to be due to thorough dealumination at high synthesis temperatures. Without wishing to be bound by theory, the Al associated with HOZ materials T The breadth of the resonances can be attributed to slight variations in the Al-O bond length due to the periodicity of the renewal of the zeolite framework, the aluminum distribution and the crystallite size.

[0131] Example 6 - Base mediated dissolution / cleavage: Base mediated dissolution studies of the parent zeolite were conducted at 130°C in the absence of surfactant to elucidate the nature of the hierarchical ordering by promoting reorganization at the unit cell level through post-synthesis assembly processes. Fig. 20A and 20B High angle XRD patterns of the parent zeolite at various stages of processing are depicted. Fig. 20A In the figure, the parent zeolite and the zeolite treated with NH4OH and urea at 130 °C for 1.5 hours. Fig. 20B Depicted are the parent zeolite after treatment with urea at 130°C for 1.5 hours, 6 hours and 18 hours. Fig. 20C Depicted as follows 29 Si MAS-NMR spectrum, and Fig.20D Depicted as follows 27 Al MAS-NMR spectra: (a) HY-15; (b) after treatment with NH4OH at 130℃ for 1.5h; (c) after treatment with urea at 130℃ / 6h. High-angle XRD study ( Fig. 20A -B) reveals that, while NH4OH almost dissolved the zeolite into an amorphous framework within 1.5 h, urea treatment resulted in partial dissolution even after 6 h. 27 Al- and 29 Si-Magic Angle Spin Nuclear Magnetic Resonance (MAS-NMR) Spectroscopy ( Fig. 20C -D) indicates that the urea treatment selectively dissolves the Si-O-Si bonds without strongly affecting the 'Si-O-Al' regions, and therefore most of the aluminum remains within the tetrahedrally coordinated framework (Al T ~60ppm). Such a dissolution pattern can lead to 4b ) or silanol extension (Q 3 ) oligomeric zeolite fragment (Q 4a , Q 3 '、Al T ), which can be easily reorganized into a crystalline mesostructure during thermal treatment. The formation of such zeolite fragments ( Fig.20E ) is a factor in the hierarchical order of making HOCMM by post-synthesis assembly process. Without wishing to be bound by theory, it is expected that in the presence of surfactant, Q 4b and Q 3 The amount of species can be significantly less.

[0132] In the case of alkali-mediated reorganization, zeolite dissolution can lead to partially crystalline oligomers, which can be recrystallized during hydrothermal (synthesis) and thermal treatment (calcination). However, uncontrolled dissolution can lead to independent amorphous domains, which cannot be recrystallized due to lack of suitable conditions (high basicity and inorganic cations). Therefore, high concentrations of strong bases such as NaOH and NH4OH can lead to uncontrolled dissolution to form amorphous components, causing pore blockage and concentration gradients throughout zeolite crystals. Due to the decrease in alkali concentration over time, low alkali concentration can lead to insufficient zeolite dissolution. As a result, strategically controlling zeolite dissolution is a factor that can be reorganized into a crystalline mesostructure in the synthesis process of HOCMM in this article.

[0133] As used herein, the phrase "major part" about a particular composition and / or solution and / or other parameters means at least about 50% and up to 100% of a unit or amount. As used herein, the phrase "significant part" about a particular composition and / or solution and / or other parameters means at least about 75% and up to 100% of a unit or amount. As used herein, the phrase "considerable part" about a particular composition and / or solution and / or other parameters means at least about 90, 95, 98 or 99 and up to 100% of a unit or amount. As used herein, the phrase "minor part" about a particular composition and / or solution and / or other parameters means at least about 1, 2, 4 or 10% of a unit or amount, up to about 20, 30, 40 or 50%.

[0134] It should be understood that the same numbers in the accompanying drawings represent the same elements in multiple drawings, and all parts and / or steps described and shown with reference to the accompanying drawings are not all embodiments or arrangements required. In addition, the terms used in this article are only used to describe the purpose of specific embodiments, and are not intended to limit the present invention. As used in this article, the singular forms "one (kind) (indefinite article a, an)" and "described (the)" are intended to also include plural forms, unless the context clearly states otherwise. It will be further understood that when used in this specification, the terms "include", "comprise", "contain", "have", "contain", "involve", and variations thereof specify the existence of stated features, integers, steps, operations, elements and / or parts, but do not exclude the existence or addition of one or more other features, integers, steps, operations, elements, parts, and / or their sets.

[0135] It should be noted that the use of ordinal terms such as "first", "second", "third", etc. to modify claim elements in the claims does not itself imply any priority, precedence or order of one claim element relative to another claim element, or the temporal order in which the actions of the method are performed, but is merely used as a label to distinguish one claim element with a specific name from another element with the same name (but using ordinal terms) to distinguish the claim elements.

[0136] It is noteworthy that the above drawings and examples are not meant to limit the scope of the present disclosure to a single implementation, because some or all of the other implementations of the elements described or shown by the interchange are also possible. In addition, in the case where some elements of the present disclosure can be partially or completely implemented using known parts, only those parts of such known parts required for understanding the present disclosure are described, and the detailed description of other parts of such known parts is omitted to avoid blurring the present disclosure. In this specification, unless otherwise clearly stated herein, the embodiment showing a single component is not necessarily limited to other implementations including a plurality of identical components, and vice versa. In addition, the applicant does not intend to attribute any term in the specification or claims to uncommon or special meanings, unless clearly stated in this manner. In addition, the present disclosure covers the current and future known equivalents of the known parts mentioned herein by way of illustration.

[0137] The foregoing description of a specific implementation will fully reveal the general nature of the present disclosure so that others can easily modify and / or adjust such specific implementations for various applications without departing from the general concept of the present disclosure by applying the knowledge of technicians in the relevant fields, without excessive experimentation. Therefore, based on the teachings and guidance presented herein, such adjustments and modifications are intended to fall within the meaning and scope of the equivalents of the disclosed implementations. It is understood that the wording or terminology herein is for descriptive and non-limiting purposes, so that the terms or wording of this specification will be interpreted by those skilled in the art according to the teachings and guidance presented herein in combination with the knowledge of technicians in the relevant fields. It should be understood that the dimensions discussed or shown are drawings according to an example, and other dimensions can be used without departing from the present disclosure.

[0138] The above-described subject matter is provided by way of illustration only and should not be construed as limiting. Various modifications and changes may be made to the subject matter described herein without following the example implementations and applications shown and described and without departing from the true spirit and scope of the invention encompassed by the present disclosure, which is defined by a set of recitations in the appended claims and by structures and functions or steps equivalent to those recitations.

[0139]

[0140]

[0141]

[0142]

[0143]

[0144]

Claims

1. A method for the synthesis of hierarchically ordered crystalline microporous materials having a high degree of long-range mesoporous order by dissolving / cutting a parent crystalline microporous material into oligomeric components and recombining them into a hierarchically ordered mesostructure, the method comprising: An effective amount of a parent crystalline microporous material having an inherent microporous structure, an effective amount of an alkaline agent, and an effective amount of a supramolecular template are mixed to form an aqueous suspension, The aqueous suspension is hydrothermally treated under conditions effective to form oligomeric units of the parent crystalline microporous material, to form shaped micelles of the supramolecular template, and to induce assembly of the oligomeric units around the shaped micelles, wherein the solid is formed into a hierarchically ordered mesostructure having a high degree of long-range mesoporous order, wherein the pores are characterized by crystalline microporous walls that retain the intrinsic microporous structure.

2. A method for the synthesis of hierarchically ordered crystalline microporous materials having a high degree of long-range mesoporous order, the method comprising: forming an aqueous suspension of an effective amount of a parent crystalline microporous material having an inherent microporous structure, an effective amount of an alkaline agent, and an effective amount of a supramolecular template, The aqueous suspension is hydrothermally treated under conditions effective for mesophase transition to dissolve / cleave the parent crystalline microporous material into oligomeric units of the parent crystalline microporous material, form shaped micelles of the supramolecular template, and reorganize the oligomeric units into a hierarchically ordered mesostructure around the shaped micelles.

3. The method as claimed in claim 1 or 2, wherein the shape of the micelle is adjusted by the selection of the supramolecular template.

4. The method as claimed in claim 1 or 2, wherein the aqueous suspension further comprises an ionic cosolute separated from an anion associated with the supramolecular template, and wherein the shape of the micelle is adjusted by the selection of the supramolecular template and the ionic cosolute.

5. The method of claim 4, wherein the ionic cosolute is selected from CO32 - 、SO4 2- 、S2O3 2- 、H2PO4 - 、F - , Cl - Br - 、NO3 - ,I - 、ClO4 - 、SCN - and C6H5O8 -3 .

6. The method as claimed in claim 4, wherein the ionic cosolute is selected from SO4 2- 、NO3 - , and ClO4.

7. The method of claim 4, wherein the ionic cosolute comprises NO3 - , and wherein the hierarchically ordered mesostructure has cubic mesophase symmetry.

8. The method of any one of claims 4 to 7, wherein the hierarchically ordered mesostructure has cubic mesophase symmetry and the mesophase transition is characterized by a surfactant packing parameter g in the range of about 0.4 to 0.8, wherein: g=V / a0l in V = the total volume of the surfactant tails of the supramolecular template, a0 = the area of ​​the head group of the supramolecular template, and l = length of the surfactant tail of the supramolecular template.

9. The method of any one of claims 4 to 7, wherein the hierarchically ordered mesostructure possesses cubic mesophase symmetry and the molar ratio of the supramolecular template to the co-solute is in the range of about 0.8 to 1.

3.

10. The method of claim 4, wherein the ionic cosolute comprises SO4 2- , and wherein the hierarchically ordered mesostructure has hexagonal mesophase symmetry.

11. The method of any one of claims 4-6 or 10, wherein the hierarchically ordered mesostructure has hexagonal mesophase symmetry and the mesophase transition is characterized by a surfactant packing parameter g in the range of about 0.4-0.6, wherein: g=V / a0l in V = the total volume of the surfactant tails of the supramolecular template, a0 = the area of ​​the head group of the supramolecular template, and l = length of the surfactant tail of the supramolecular template.

12. The method of any one of claims 4-6 or 10, wherein the hierarchically ordered mesostructure possesses hexagonal mesophase symmetry and the molar ratio of the supramolecular template to the co-solute is in the range of about 0.8-1.

3.

13. The method of claim 4, wherein the ionic cosolute comprises ClO4 - , and wherein the hierarchically ordered mesostructure possesses layered mesophase symmetry.

14. The method of any one of claims 4 to 6 or 13, wherein the hierarchically ordered mesostructure possesses lamellar mesophase symmetry and the mesophase transition is characterized by a surfactant packing parameter g in the range of about 0.9-1.1, wherein: g=V / a0l in V = the total volume of the surfactant tails of the supramolecular template, a0 = the area of ​​the head group of the supramolecular template, and l = length of the surfactant tail of the supramolecular template.

15. The method of any one of claims 4 to 6, or 13, wherein the hierarchically ordered mesostructure possesses lamellar mesophase symmetry and the molar ratio of supramolecular template to cosolute is in the range of about 0.2-0.

7.

16. The method of any one of claims 1 to 15, wherein the supramolecular template is a bulky surfactant having one or more dimensions larger than the dimensions of the micropores of the crystalline microporous material to restrict diffusion into the micropores of the crystalline microporous material, wherein the dimensions relate to a head group of the surfactant, a tail group of the surfactant, or a co-template.

17. The method of claim 16, wherein the supramolecular template contains at least one moiety as a head group or a tail group, the moiety being selected from the group consisting of organosilanes, hydroxysilyls, alkoxysilyls, aromatic compounds, branched alkyls, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing moieties.

18. The method as claimed in claim 16 or 17, wherein the supramolecular template contains at least one cationic moiety selected from a quaternary ammonium moiety and a phosphonium moiety.

19. The method of claim 16 or 17, wherein the supramolecular template contains at least one quaternary ammonium group having a terminal alkyl group having 6 to 24 carbon atoms.

20. The method of claim 16 or 17, wherein the supramolecular template contains two quaternary ammonium groups, wherein the alkyl group bridging the quaternary ammonium groups contains 1-10 carbon atoms.

21. The method of claim 16, wherein the supramolecular template contains at least one quaternary ammonium group and at least one head group moiety selected from the group consisting of organosilanes, hydroxysilyls, alkoxysilyls, aromatic compounds, branched alkyls, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing moieties.

22. The method of claim 16, wherein the supramolecular template contains at least one quaternary ammonium group and at least one head group moiety, wherein the head group moiety is selected from the group consisting of organosilanes, hydroxysilyls, alkoxysilyls, aromatic compounds, branched alkyls, sulfonates, carboxylates, phosphates, and combinations comprising one of the foregoing moieties, wherein the alkyl group bridging at least one of the quaternary ammonium groups and at least one of the head groups contains 1-10 carbon atoms.

23. The method of claim 16, wherein the supramolecular template comprises dimethyloctadecyl(3-trimethoxysilyl-propyl)-ammonium, or a derivative of dimethyloctadecyl(3-trimethoxysilyl-propyl)-ammonium.

24. The method of any one of claims 1 to 23, wherein the alkaline agent is provided in the aqueous suspension at a concentration of about 0.1-5% by weight and is selected from ammonia, ammonium hydroxide and urea.

25. The method of any one of claims 1 to 23, wherein the alkaline agent is urea, wherein during the hydrothermal treatment, the urea reacts to form ammonium hydroxide, thereby controlling the hydrothermal treatment.

26. A method as claimed in any one of claims 1 to 23, wherein the as-formed hierarchically ordered mesostructure is calcined.

27. A method as claimed in claim 26, wherein calcination reduces the amorphous content of the hierarchically ordered mesostructure.

28. The method of any one of claims 1-27, wherein the parent crystalline microporous material comprises a zeolite or a zeolite-type material.

29. The method of any one of claims 1 to 27, wherein the parent crystalline microporous material is a zeolite having a framework selected from the group consisting of AEI, *BEA, CHA, FAU, MFI, MOR, LTL, LTA and MWW.

30. The method of any one of claims 1-27, wherein the parent crystalline microporous material is a zeolite having a FAU framework.

Citation Information

Patent Citations

  • Hierarchically ordered crystalline microporous materials with long-range mesoporous order having cubic symmetry

    US12152204B2

  • Hierarchically ordered crystalline microporous materials with long-range mesoporous order having hexagonal symmetry

    US20240009657A1

  • Hierarchically ordered crystalline microporous materials with long-range mesoporous order having lamellar symmetry

    US20240010504A1